Spherical iron alloy powder material, its manufacturing method and use

Through the rapid solidification and selective element dissolution, the problem of difficulty in producing spherical ferroalloy powders in traditional methods is solved, and the low-cost and efficient production of spherical ferroalloy powders suitable for multiple fields is achieved.

JP2025504532APending Publication Date: 2025-02-12赵远云
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024543990
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2022-10-31
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

It is difficult to effectively produce spherical ferroalloy powders with particle sizes less than 10 μm, especially spherical ferroalloy powders at the nanoscale, and the traditional methods are costly and complex in operation.

Method used

By selecting the alloy melt composed of specific elements for rapid solidification, a structure containing La-rich matrix phase and dispersible phases such as Fe, Cr, V is formed. The rapid solidification and selective dissolution of elements are obtained to obtain ferroalloy powders that are mainly spherical or nearly spherical.

Benefits of technology

It has achieved low-cost and high-efficiency production of spherical ferroalloy powders with particle sizes from nanometers to microns, improving powder flowability and uniformity, and is suitable for powder metallurgy, powder coating, metal injection molding and 3D printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504532000001_ABST
    Figure 2025504532000001_ABST
Patent Text Reader

Abstract

The present invention relates to a spherical iron alloy powder material and its manufacturing method and use. By selecting a main alloy system of Fe and La, and simultaneously adding special alloy spheroidizing precipitation elements and corrosion-resistant elements, during the solidification process of the alloy, a spherical dispersed particle phase in which Fe-rich spherical precipitation elements are solid-dissolved in the initial alloy melt is achieved, and dispersed precipitation is achieved in the La-rich matrix phase. By removing the La-rich matrix phase, a spherical iron alloy powder material with a particle size of nanometers to tens of microns is obtained. The above manufacturing method is a simple process and can produce a variety of spherical iron alloy powders with different morphologies in the nano-order, submicron-order, and micron-order, and has good application prospects in the fields of powder metallurgy, metal injection molding (MIM), 3D printing, magnetic materials, heat-resistant materials, high-temperature alloys, paints, electric heating materials, wave absorbing materials, magnetic fluid materials, etc.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of metal powder materials, in particular to a spherical iron alloy powder material and its manufacturing method and use. [Background technology]

[0002] Fe alloys are the most widely used metallic materials. Using micro-nanoparticle-sized Fe alloy powder as raw material, a large number of Fe alloys with various properties can be manufactured by additive manufacturing techniques such as powder metallurgy, metal injection molding (MIM), and 3D printing. Examples include Fe-Cr ferritic stainless steel, Fe-Cr-Ni austenitic stainless steel, Fe-Cr-Al electric heating alloy, Fe-Cr-Co permanent magnet, and Fe-Cr-Si soft magnetic material.

[0003] Spherical or near-spherical Fe alloy particles have become important raw materials in the application fields of powder metallurgy, powder coating, metal injection molding (MIM), 3D printing, magnetic materials, etc., due to their excellent flowability, homogeneity, and powder layering densification. In many cases, spherical or near-spherical particles need to be used as raw materials to obtain the desired application effect of the final material. At present, spherical Fe alloy powder materials are mainly produced by the atomization method, that is, a method in which liquid metal or alloy is directly pulverized using a high-speed fluid to obtain metal powder. However, due to the limited atomization ability of the atomization method, it is generally only suitable for producing spherical Fe alloy powder with a particle size of 10 μm to 150 μm. For spherical Fe alloy powder materials with a particle size of less than 10 μm, especially nano to several microns (10 μm or less), it is difficult or impossible to produce them by the atomization method. Therefore, it is of great significance to develop a method for producing ultrafine spherical iron alloy powder materials with a particle size of nanometers to several micrometers. Summary of the Invention [Problem to be solved by the invention]

[0004] Based on this, in order to address the above technical problems, there is a need to provide a method for producing spherical iron alloy powder material, which has a simple process, low cost and easy operation. [Means for solving the problem]

[0005] In order to solve the above technical problems, the present invention proposes the following technical content.

[0006] A first aspect is a method for producing a spherical iron alloy powder material, the method comprising the steps of:

[0007] Step 1: Select an initial alloy raw material, melt the initial alloy raw material according to the initial alloy composition ratio, and obtain a homogeneous initial alloy melt. The main composition of the initial alloy melt is La x Fe y T z M a D b where T includes at least one of Cr and V, M includes at least one of Al, Ni, Co and Si, D includes at least one of Mo, W and Ti, x, y, z, a and b are the atomic percentage contents of the corresponding elements, and 18%≦x≦95.8%, 4%≦y≦81.8%, 0.1%≦z≦35%, 0≦a≦40%, 0≦b≦15%.

[0008] Step 2: The initial alloy melt is solidified into an initial alloy solid by a rapid solidification technique, and the solidification structure of the initial alloy solid includes a matrix phase and a dispersed particle phase, the matrix phase has a melting point lower than that of the dispersed particle phase, the dispersed particle phase is encapsulated in the matrix phase, and the percentage content of the matrix phase in the solidification structure is 40% or more. The average composition of the matrix phase is mainly La x1 M a1 The composition of the dispersed particle phase is mainly Fe y2 T z2 M a2 D b2 La x2where x1, a1, x2, y2, z2, a2, and b2 are the atomic percentage contents of the corresponding constituent elements, and 45% ≤ x1 ≤ 100%, 0% ≤ a1 ≤ 55%, 50% ≤ y2 ≤ 98%, 0.2% ≤ z2 < 50%, 0% ≤ a2 ≤ 30%, 0% ≤ b2 ≤ 35%, and 0 < x2 ≤ 5%. The above dispersion particle phase contains a substantial amount of spherical or nearly spherical dispersion particle phases, and a part of the spherical or nearly spherical dispersion particle phases contains specific dendritic features. The particle size of the above dispersion particle phase is 5 nm to 50 μm.

[0009] Step 3: Remove the matrix phase from the above initial alloy solid, mainly retaining the dispersion particle phase, Fe y2 T z2 M a2 D b2 La x2 to obtain an iron alloy powder material mainly composed of. Here, 50% ≤ y2 ≤ 98%, 0.2% ≤ z2 < 50%, 0% ≤ a2 ≤ 30%, 0% ≤ b2 ≤ 35%, and 0 < x2 ≤ 5%. The above iron alloy powder particles contain a substantial amount of spherical or nearly spherical particles, and a part of the spherical or nearly spherical iron alloy powder particles contains specific dendritic features. The particle size of the above iron alloy powder particles is 5 nm to 50 μm.

[0010] In the above step 1, Furthermore, the above T contains Cr, and furthermore, T contains V.

[0011] Furthermore, the above M contains Al, and furthermore, M contains Ni, and furthermore, M contains Co.

[0012] Furthermore, the above M contains Si.

[0013] Furthermore, 0 < a ≤ 40%. Furthermore, 2.5% < a ≤ 40%, 18% ≤ x ≤ 93.3%. Furthermore, 5% < a ≤ 40%, 18% ≤ x ≤ 90.8%. Furthermore, 10% < a ≤ 40%, 18% ≤ x ≤ 85.8%.

[0014] Furthermore, the above D contains Mo, and furthermore, D contains W, and furthermore, D contains Ti.

[0015] In addition, 0 <b≦15%である。さらに、0.5%<b≦15%、18%≦x≦95%である。

[0016] Furthermore, 18%≦x≦93.8% and 6%≦y≦81.8% are satisfied. Preferably, 18%≦x≦89.8% and 10%≦y≦81.8% are satisfied.

[0017] Further, 18%≦x≦95% and 0.5%≦z≦35%. Further, 18%≦x≦94% and 1%≦z≦35%. Preferably, 18%≦x≦92% and 3%≦z≦35%. Preferably, 18%≦x≦90% and 5%≦z≦35%.

[0018] Furthermore, 18%≦x≦80%. Furthermore, 18%≦x≦70%. Furthermore, 18%≦x≦60%. Furthermore, 18%≦x≦50%.

[0019] Since the rare earth La is a large atom, even if its atomic percentage content in the initial alloy melt is low, it corresponds to a large volume percentage content, which is the key to the diffusion distribution of the dispersed particle phase. For example, La 20 Fe 75 For an alloy with atomic percent composition of Cr5, based on the atomic weight and density of the elements, the volume percent content of La matrix can be calculated to be 44.35%. The volume percent content of the matrix phase will further increase when most of the M element also enters the matrix phase.

[0020] Furthermore, y>z, i.e. the atomic percentage content of Fe in the initial alloy melt is higher than the atomic percentage content of T element.

[0021] In the above step 2, According to the phase diagrams of La-Fe, La-Cr, La-V, Fe-Cr, Fe-V, and Cr-V, the melting points of Fe, Cr, and V are all higher than that of La, Fe, Cr, and V do not form intermetallic compounds with La, and are obviously not solid-soluble, and Fe-Cr, Fe-V, and Cr-V are all infinite solid-solution alloy systems. Therefore, during the solidification process of the initial alloy melt, a dispersed particle phase mainly composed of Fe, Cr, and V is first precipitated from the alloy melt, and a matrix phase mainly composed of La is solidified last, and the alloy solidification structure does not contain intermetallic compounds composed of La and Fe, Cr, and V. That is, in the process of solidifying the initial alloy melt into an initial alloy solid by the rapid solidification method, the solidification structure of the initial alloy solid includes a La-rich matrix phase and an Fe-rich, Cr-rich, or (and) V-rich dispersed particle phase, the melting point of the matrix phase is lower than that of the dispersed particle phase, and the dispersed particle phase is encapsulated in the matrix phase.

[0022] Further, the solidification rate of the initial alloy melt is higher than 20 K / s, preferably, the solidification rate of the initial alloy melt is higher than 50 K / s, preferably, the solidification rate of the initial alloy melt is higher than 100 K / s, preferably, the solidification rate of the initial alloy melt is higher than 250 K / s; more preferably, the solidification rate of the initial alloy melt is higher than 500 K / s.

[0023] Furthermore, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 10 mm. Preferably, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 5 mm. Preferably, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 2 mm. Preferably, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 1 mm. Preferably, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 500 μm. Preferably, the shape of the initial alloy solid has at least one dimension in a three-dimensional scale direction that is less than 100 μm.

[0024] The faster the solidification rate of the initial alloy melt, the smaller the minimum scale of the three-dimensional shape of the resulting initial alloy solid. For example, a ribbon of the initial alloy solid having a thickness of about 25 μm can be formed by a method of forming a thin strip of about 10 μm. 6 K / s~about 10 7 K / s solidification rate, alloy rods with a diameter of about 5 mm or plates with a thickness of about 5 mm can be obtained by copper roll-fling strip method, and alloy bars with a diameter of about 5 mm or plates with a thickness of about 5 mm can be obtained by copper mold casting .... Generally speaking, the grain size of the dispersed grain phase is negatively correlated with the solidification rate of the initial alloy melt, that is, the larger the solidification rate of the initial alloy melt, the smaller the grain size of the dispersed grain phase. However, different solid solutions of different elements, or different solid solution amounts of the same element, may inhibit the normal growth of the dispersed grain phase in certain aspects in different ways, which may cause some changes in the law. For example, due to the tendency of spheroidization, the grain phase may fuse and re-spheroidize during the solidification process, or the nucleation rate may be inhibited and the growth rate may be increased. For example, when a certain element is not solid-dissolved, the average grain size of the dispersed grain phase obtained at a given cooling rate is 1 μm, but after solid-dissolving a certain element, a spherical dispersed grain phase can be obtained at the same cooling rate, and the average grain size of the grain phase is 5 μm.

[0025] Furthermore, the shape of the initial alloy solid includes at least one of a strip, a band, a flake, a filament, and a granule, and preferably, the shape of the initial alloy solid includes at least one of a strip, a band, and a flake.

[0026] Further, the solidification method of the initial alloy melt includes at least one of melt flying belt, rapid solidification flying sheet, casting, continuous casting, atomization powdering, and melt pumping.

[0027] Furthermore, the initial alloy solid is in the form of a strip, and the thickness of the strip is 5 μm to 5 mm.

[0028] Furthermore, the volume percentage content of the matrix phase during solidification is 45% or more, and furthermore, the volume percentage content of the matrix phase during solidification is 50% or more.

[0029] Furthermore, 0 < x2 < x < x1, that is, in the solidification process of the initial alloy melt, La is enriched in the matrix phase and a small amount of La exists in the dispersed particle phase.

[0030] Since La is a large atom in the matrix phase, even when the atomic percentage content of La in the matrix phase is as low as 45%, the volume percentage content of La far exceeds 50%, so the matrix phase still has La as the main component.

[0031] Furthermore, 50% ≤ x1 ≤ 100%, 0% ≤ a1 ≤ 50%.

[0032] Furthermore, the La element is in y2 T z2 M a2 D b2 La x2 dissolved and present in the dispersed particle phase.

[0033] Furthermore, 0 < x2 ≤ 3%.

[0034] Furthermore, 0 < y < y2, that is, in the solidification process of the initial alloy melt, Fe is in y2 T z2 M a2 D b2 La x2 enriched in the dispersed particle phase.

[0035] Furthermore, 50% ≤ y2 ≤ 95%. Furthermore, 50% ≤ y2 ≤ 90%. Furthermore, 50% ≤ y2 ≤ 85%. Furthermore, 50% ≤ y2 ≤ 75%.

[0036] Furthermore, 0 < z < z2, that is, in the solidification process of the initial alloy melt, the T element is in Fe y2 T z2 M a2 D b2 Lax2 It is enriched in the dispersed particle phase.

[0037] Furthermore, 1% ≤ z2 < 50%. Furthermore, 3% ≤ z2 < 50%. Furthermore, 5% ≤ z2 < 50%. Furthermore, 10% ≤ z2 < 50%.

[0038] Furthermore, y2 > z2, that is, Fe y2 T z2 M a2 D b2 La x2 The atomic percentage content of Fe in the dispersed fine particle phase is higher than the atomic percentage content of the T element.

[0039] Furthermore, the T element is Fe y2 T z2 M a2 D b2 La x2 It exists in solid solution in the dispersed particle phase.

[0040] Furthermore, when a = 0, a2 = a1 = 0, 0 < a ≤ 40%, 0 < a2 < a1, that is, in the solidification process of the initial alloy melt, the M element is La x1 M a1 It is enriched in the matrix phase, and at the same time, the M element is Fe y2 T z2 M a2 D b2 La x2 It has a certain content in the diffusion particle phase.

[0041] Furthermore, 1% ≤ a2 ≤ 30%. Furthermore, 3% ≤ a2 ≤ 30%. Furthermore, 5% ≤ a2 ≤ 30%. Furthermore, 10% ≤ a2 ≤ 30%.

[0042] Furthermore, the M element is Fe y2 T z2 M a2 D b2 La x2 It exists in solid solution in the dispersed particle phase.

[0043] In the solidification process of the initial alloy melt, the M element is such that the M element is La x1 Ma1 Enriched in the matrix phase, and at the same time, a considerable amount of element M is in Fe y2 T z2 M a2 D b2 La x2 It is characterized by solid-solubilizing in the dispersed particle phase.

[0044] Furthermore, when b = 0, b2 = b = 0, 0 < b ≤ 15%, 0 < b < b2, that is, in the solidification process of the initial alloy melt, element D is in Fe y2 T z2 M a2 D b2 La x2 Enriched in the dispersed particle phase.

[0045] Furthermore, 0.5% ≤ b2 ≤ 35%. Furthermore, 1% ≤ b2 ≤ 35%. Furthermore, 5% ≤ b2 ≤ 35%.

[0046] Furthermore, element D is in Fe y2 T z2 M a2 D b2 La x2 Exists in a solid-solved state in the dispersed particle phase.

[0047] Specifically, when 0 < a ≤ 40%, according to the Al-Fe phase diagram and the Si-Fe phase diagram, the solid solubility of Al and Si in Fe is large, and Fe-Ni and Fe-Co are completely solid-soluble. Therefore, element M can be solid-solved in the Fe-rich dispersed particle phase. According to the Al-La phase diagram, Ni-La phase diagram, Co-La phase diagram, and Si-La phase diagram, Al, Ni, Co, and Si can all form La-rich intermetallic compounds with La. Since the melting point of the La-rich intermetallic compound is lower than that of the Fe-rich dispersed particles, in the initial alloy melt solidification process, first, a certain amount of element M is solid-solved in the Fe-rich dispersed particle phase, and the remaining element M is combined with La to form a La-rich intermetallic compound matrix. When La still exists in excess, the Lax1Ma1 matrix phase contains not only the La-rich intermetallic compound formed by element M and La but also the excess La phase.

[0048] When 0 < b ≤ 15%, according to the phase diagrams of La-Ti, La-W, and La-Mo, none of Ti, W, and Mo form intermetallic compounds with La and do not dissolve significantly. Therefore, Ti, W, and Mo do not enter the La-rich matrix phase during the solidification of the initial alloy melt. According to the Fe-Ti, Fe-Mo, and Fe-W phase diagrams, the solid solubility of Ti and W in Fe is about 10 at.%, and the solid solubility of Mo in Fe is about 20 at.%. At the same time, according to the Cr-Ti, Cr-Mo, and Cr-W phase diagrams, Cr and Ti, Mo, W are completely mutually soluble, and according to the V-Ti, V-Mo, and V-W phase diagrams, V and Ti, Mo, W are completely mutually soluble. Therefore, the elemental affinity between the D elements Ti, W, and Mo and La is extremely poor, the affinity with Fe is good, and the affinity with Cr and V is excellent. When the initial alloy melt contains the D elements and Fe, Cr, and V elements, during the solidification process of the initial alloy melt, the selected D elements are enriched in the Fe y2 T z2 M a2 D b2 La x2 enriched in the dispersed particle phase.

[0049] Note that Ti, Zr, and Hf are homologous elements. Zr and Hf do not form intermetallic compounds with La and do not dissolve significantly. However, unlike Ti, Zr and Hf also hardly dissolve in Fe, Cr, and V. Therefore, Zr and Hf can only form intermetallic compounds with each other. Therefore, when Zr and Hf are contained in the initial alloy melt, Zr and Hf are hardly dissolved in the Fe y2 T z2 M a2 D b2 La x2 dispersed particle phase and, as shown in Comparative Example 3, Fe y2 T z2 M a2 D b2 La x2 In addition to the dispersed particle phase, dendritic intermetallic compound phases of Zr and Hf with Fe, Cr, and V are additionally formed. None of these intermetallic compounds are the iron alloy phase mainly composed of the solid solution alloy that the present invention focuses on.

[0050] Similarly, Nb, Ta, and V are all elements of the same group. Nb and Ta do not form intermetallic compounds with La, and do not form significant solid solutions with La. However, unlike Mo, W, Ti, and V, the solid solubility of Nb and Ta in Fe, Cr, and V is extremely low, so Nb and Ta can only form intermetallic compounds with each other. Therefore, if the initial alloy melt contains Nb and Ta, Fe y2 T z2 M a2 D b2 La x2 The solid solubility of Nb and Ta in the dispersed particle phase is very low, and only very small amounts or none can be present. As shown in Comparative Example 4, when the initial alloy melt contains more Nb and Ta, Fe y2 T z2 M a2 D b2 La x2 In addition to the possible presence of very small amounts of Nb and Ta in the dispersed particle phase, dendritic intermetallic phases of Nb and Ta with Fe, Cr, and V are additionally formed. None of these intermetallic compounds are the iron alloy phases that are the main solid solution alloys on which this invention focuses.

[0051] The initial alloy melt contains only La and Fe, and the solidification rate of the alloy melt is 10 6 At a cooling rate higher than K / s, a certain amount of nanoscale (90 nm or less) nearly spherical Fe phase particles with insufficient dendrite growth is obtained. This is because at such a high cooling rate, even if the Fe phase particles have a strong tendency to form dendrites, they grow too slowly and solidify and precipitate at the nanoscale as nearly spherical Fe phase particles with insufficient dendrite growth. However, since both La and Fe are easily oxidized, they are highly reactive with acid solutions and easily dissolved. Therefore, even if an initial alloy solid consisting of nearly spherical Fe phase particles of 90 nm or less and a La matrix is ​​produced at an ultra-high solidification rate, it is difficult to separate the La matrix and the nanoscale nearly spherical Fe phase particles by reactive dissolution in an acid solution and retain the nanoscale nearly spherical Fe phase particles (the nanoscale Fe phase particles are also dissolved).

[0052] In general, the solidification rate of a simple La-Fe alloy melt is 106 If the solidification rate is lower than 10 K / s, only dendritic Fe phase particles are obtained, and it is difficult to obtain spherical or nearly spherical Fe phase particles. 5 Even if the solidification rate is as high as 500 K / s and a La-Fe alloy band of about 100 μm is obtained, the shape of the dispersed particle phase is still mainly dendritic (see Comparative Example 2). Also, when the solidification rate of the La-Fe alloy melt is lower than 500 K / s, the dispersed particle phase is a dendritic phase with a large grain size that has grown sufficiently, and after the matrix phase is removed, the Fe phase obtained in the form of dendrites is obtained by intertwining with dendritic fibers (see Comparative Example 1).

[0053] When the initial alloy melt contains La and Fe, and at the same time contains Cr, V, Mo, W, Ti elements with high melting points, especially when it contains Cr or (and) V that can form a complete solid solution with Fe, the initial alloy melt will first precipitate Fe-rich primary crystals in solid solution with T element during solidification. The special solid solution of T element destroys the original crystal lattice formation rules and inhibits the growth of Fe-rich dendritic phase along a specific crystal plane orientation, so that Fe-rich primary crystal particles in solid solution with T element tend to be spheroidized. The higher the content of T element in solid solution in Fe-rich primary crystal, the larger the spherical or nearly spherical dispersed particle phase can be obtained at a low melt cooling rate. Therefore, T element is the key to the spheroidization of Fe-rich primary crystal particles found in the present invention, especially when the size of Fe-rich dispersed particles is large.

[0054] Furthermore, the T element contains at least one of the corrosion-resistant elements Cr and V, and stainless steel is formed when these elements are dissolved in Fe (the corrosion resistance of V is even higher than that of Cr). Therefore, the dissolution of the T element significantly improves the corrosion resistance of the Fe-rich dispersed particle phase. Since the matrix phase is mainly composed of La, which has high corrosion resistance, the matrix phase can be easily removed by reactive corrosion by reacting it with an acid solution of a certain concentration, and dispersed Fe-rich phase dispersed particles can be obtained. When the corrosion resistance of the Fe-rich phase dispersed particles is significantly improved, 10 6By using a cooling rate of more than 1000 K / s, an initial alloy solid containing a nano-Fe-rich spherical particle phase containing elements T and D can be produced. At the same time, taking advantage of the high corrosion resistance of the nano-Fe-rich spherical particle phase containing elements T and D, the phase can be separated from the La-rich matrix by an acid reaction to obtain nano-scale Fe-rich spherical particles.

[0055] The M elements include at least one of Al, Ni, Co, and Si, which are the main elements of commercial iron alloys. For example, Al is one of the main elements of Fe-Cr-Al electric heating alloys and thermal spray coatings, Ni is one of the main elements of austenitic stainless steel Fe-Cr-Ni, Co is one of the main elements of Fe-Cr-Co permanent magnets, and Si is one of the main elements of Fe-Cr-Si soft magnetic materials. According to actual research results, during the solidification process of the initial alloy melt, the matrix is ​​also enriched with more M elements, so the atomic percentage solid solution content of Si in the Fe-rich phase dispersion particles generally does not exceed 8%, and a large amount of Si needs to be added in the initial alloy melt to achieve it. The atomic percentage solid solution content of Ni in the Fe-rich phase dispersion particles generally does not exceed 12%, and both Al and Co have significant solid solution content in the Fe-rich phase dispersion particles (see examples), and the atomic percentage solid solution content can even exceed 20%. Since many of the commercially available iron alloys mentioned above have low requirements for the content of the M element, it is possible to produce commercially available iron alloy powders that satisfy the above-mentioned relevant components.

[0056] When the initial alloy melt contains M element, some M element also exists in Fe-rich phase disperse particles through solid solution, so that M element generally has a positive effect on the spheroidization of Fe-rich phase disperse particles (see Example 13 and Example 14). In addition, M-like elements and La are easily reactive with acid solution, so that M element and La can be removed from the matrix phase by acid etching reaction to obtain freely dispersed Fe-rich phase disperse particles. In addition, by utilizing the difference in chemical activity between La and M element, and by using the dealloying principle to mainly remove only La in the matrix phase by appropriate acid solution, a composite powder with freely dispersed Fe-rich disperse particles and nanoporous can be obtained.

[0057] D elements include high melting point Mo, W, and Ti elements, which are not as soluble in Fe as T elements (T elements are completely soluble in Fe), but the solubility rate of D elements in Fe is 10-20%, and D elements are completely soluble in T elements. Therefore, by appropriately adding high melting point Mo, W, and Ti elements to the initial alloy melt, the sphericity and corrosion resistance of Fe-rich phase dispersion particles can be significantly improved, and at the same time, the melting point and heat resistance of Fe-rich phase dispersion particles can be significantly improved. For example, the role of Ti in the commercially available austenitic stainless steel 1Cr18Ni9Ti and the role of Mo in the commercially available ultra-high temperature Fe-Cr-Al-Mo electric heating alloy.

[0058] In summary, in this invention, based on the La-Fe alloy, the types of T element, M element and D element are the result of careful design and selection. With such selection, during the solidification process of the initial alloy melt, Fe, T element and D element are all mainly composed of Fe. y2 T z2 M a2 D b2 La x2 The M element exists in the dispersed particle phase and is partially composed of Fe y2 T z2 M a2 D b2 La x2 La and M elements are mainly present in the dispersed particle phase. x1 M a1 At the same time, Fe y2 T z2 M a2 D b2 La x2 In the dispersed particle phase, the M element also has a significant solid solubility, while La has a low solid solubility. This ingenious design ensures that the T element promotes the spheroidization of dispersed particles, while at the same time improving the corrosion resistance and helping to separate the dispersed particle phase from the matrix phase through the corrosion reaction.

[0059] The spheroidization of the Fe-rich dispersoid phase is achieved by the solid solution alloying of special elements and the adjustment of the melt cooling rate to suppress the formation and growth of the Fe-rich dendritic phase, so the higher the content of the T element solid-solubilized in the Fe-rich dispersoid phase, or the higher the total content of the solid solution elements including the T element, or the faster the cooling rate of the melt, the easier it is to form a spherical or near-spherical Fe-rich dispersoid phase. Therefore, to obtain the same spheroidization effect, a lower cooling rate can be used when the content of the solid solution elements in the Fe-rich dispersoid phase is high, and a higher cooling rate can be used when the content of the solid solution elements is lower. In fact, by adjusting the parameters, the volume percentage content of the spherical or near-spheroid dispersoid phase among all the dispersoid phases can be as close as possible to 100%, but it cannot reach 100%.

[0060] Furthermore, the spherical or nearly spherical dispersed particle phase has a sphericity of more than 50%.

[0061] Furthermore, the spherical or nearly spherical dispersed particle phase has a sphericity of more than 70%.

[0062] Furthermore, the spherical or nearly spherical dispersed particle phase has a sphericity of more than 85%.

[0063] Furthermore, the spherical or nearly spherical dispersed particle phase has a sphericity of more than 95%.

[0064] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 10%.

[0065] Note: For convenience of expression, the term "spherical" or "spherical or nearly spherical" may be used. In reality, an ideal sphere does not exist, so in this application, "spherical" includes spherical and nearly spherical shapes.

[0066] In simple La-Fe alloys, it is difficult to obtain spherical dispersed particle phases by the above methods, or a very high cooling rate is required to obtain nearly spherical Fe phase particles of 90 nm or less, and it is also difficult to expel such nanoparticles by acid reaction with the La matrix (Fe nanoparticles also react with acid and become soluble). Therefore, if the volume percentage content of spherical or nearly spherical dispersed particle phases in the total dispersed particle phase exceeds 10% after the addition of corrosion-resistant elements Cr and / or V, or after the simultaneous addition of more D elements, through alloy design, it is considered that a considerable amount of spherical or nearly spherical dispersed particle phases has been obtained.

[0067] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 25%.

[0068] Furthermore, the dispersed particle phase is predominantly spherical or near-spherical in shape.

[0069] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 50%.

[0070] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 75%.

[0071] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 90%.

[0072] Furthermore, the volume percentage content of the spherical or nearly spherical dispersed particle phase in the total dispersed particle phase is greater than 95%.

[0073] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 2%, or when the total content of solute elements including T elements exceeds 4%, and when the cooling rate of the melt exceeds 500 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 50% of the total dispersoid phase.

[0074] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 4%, or when the total content of solute elements including T elements exceeds 8%, and when the cooling rate of the melt exceeds 250 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 50% of the total dispersoid phase.

[0075] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 8%, or when the total content of solute elements including T elements exceeds 12%, and when the cooling rate of the melt exceeds 100 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 50% of the total dispersoid phase.

[0076] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 12%, or when the total content of solute elements including T elements exceeds 18%, and when the cooling rate of the melt exceeds 50 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 50% of the total dispersoid phase.

[0077] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 16%, or when the total content of solute elements including T elements exceeds 25%, and when the cooling rate of the melt exceeds 20 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 50% of the total dispersoid phase.

[0078] In general, when the content of solute T elements in the Fe-rich dispersoid phase exceeds 16%, or when the total content of solute elements including T elements exceeds 25%, and when the cooling rate of the melt exceeds 100 K / s, the volume percentage content of the spherical or near-spherical dispersoid phase exceeds 95% of the total dispersoid phase.

[0079] Furthermore, even when the average particle size of the dispersed particle phase exceeds 0.25 μm, a dispersed particle phase having a sphericity of more than 85% can be obtained.

[0080] Furthermore, even when the average particle size of the dispersed particle phase exceeds 0.25 μm, it is possible to obtain a dispersed particle phase with a sphericity of more than 85% by adjusting the cooling rate and the alloy composition.

[0081] Furthermore, even when the average particle size of the dispersed particle phase exceeds 0.5 μm, it is possible to obtain a dispersed particle phase with a sphericity of more than 85% by adjusting the cooling rate and the alloy composition.

[0082] Furthermore, even when the average particle size of the dispersed particle phase exceeds 1 μm, it is possible to obtain a dispersed particle phase with a sphericity of more than 85% by adjusting the cooling rate and the alloy composition.

[0083] Furthermore, even when the average particle size of the dispersed particle phase exceeds 3 μm, it is possible to obtain a dispersed particle phase with a sphericity of more than 85% by adjusting the cooling rate and the alloy composition.

[0084] Furthermore, the partially spherical or nearly spherical dispersed particle phase contains specific dendritic features, which means that the partially spherical or nearly spherical dispersed particle phase grows short, protruding dendrites, giving the entire spherical or nearly spherical dispersed particle phase a shape similar to that of the "coronavirus" virus (the protruding dendrites growing on the spherical or nearly spherical dispersed particle phase correspond to the corona of the "coronavirus" sphere).

[0085] Furthermore, the number of the protruding short dendrites is one or more, and the length of the further convexity calculated from the spherical surface is less than the radius of the spherical particle. For specific shapes, see the embodiments.

[0086] Furthermore, the number of short convex dendrites is one or more, and the length of the further convexity calculated from the sphere is less than half the radius of the spherical particle.

[0087] Although such insufficiently spheroidized protuberances have some effect on the spheroidization of the granular phase, the spherical granular phase on which the protuberances grow dependently has a high degree of sphericity itself, with short protuberances and generally distributed symmetrically and uniformly on the particle surface. Therefore, even if some of the spherical or near-spherical dispersed particle phase contains insufficiently spheroidized convex short dendritic features, such particles are still spherical or near-spherical particles with a high degree of sphericity and belong statistically to the category of spherical or near-spherical particles.

[0088] Furthermore, the dispersed particle phase is predominantly spherical or near-spherical in shape. In addition, the dispersed particle phase contains a small amount of a typical dendritic particle phase. The dendritic particles are typical of dendritic shapes and do not appear to be spherical and do not belong to the statistical category of spherical or near-spherical particles.

[0089] The dispersed particle phase is mainly spherical or near-spherical in shape, a part of the spherical or near-spherical dispersed particle phase contains specific dendritic features, and at the same time, the dispersed particle phase contains a small amount of typical dendritic particle phase. The presence of these two types of dendritic morphology features is a unique feature of the iron-rich dispersed particle phase obtained according to the present invention.

[0090] Furthermore, the length of the short dendrites that protrude further from the spherical surface is less than one-third the radius of the spherical particle.

[0091] Furthermore, the length of the short dendrites that protrude further from the spherical surface is less than one-fifth of the radius of the spherical particle.

[0092] Furthermore, the particle size range of the dispersed particle phase is 5 nm to 40 μm.

[0093] Furthermore, the particle size range of the dispersed particle phase is 5 nm to 30 μm.Further, the particle size range of the dispersed particle phase is 5 nm to 20 μm.Further, the particle size range of the dispersed particle phase is 5 nm to 10 μm.

[0094] Furthermore, the particle size range of the dispersed particle phase is 100 nm to 50 μm.

[0095] Furthermore, the particle size range of the dispersed particle phase is 250 nm to 50 μm.

[0096] Furthermore, the particle size range of the dispersed particle phase is 500 nm to 50 μm.

[0097] Furthermore, the particle size of the dispersed particle phase is in the range of 5 nm to 100 nm.

[0098] Furthermore, the particle size of the dispersed particle phase is in the range of 5 nm to 50 nm.

[0099] The particle size of the dispersed particle phase is negatively correlated with the solidification rate of the initial alloy melt, i.e., the higher the solidification rate of the initial alloy melt, the smaller the particle size of the dispersed particle phase. Thus, the smaller the particle size of the dispersed particle phase, the faster the solidification rate of the initial alloy melt, and the corresponding faster the spheroidization rate of the dispersed particle phase, resulting in a higher volume percentage content of spherical or near-spherical dispersed particle phase in the total dispersed particle phase.

[0100] Furthermore, the number of single crystal particles in the particle-dispersed phase accounts for 60% or more of the total number of particles.

[0101] In the above step 3, Fe y2 T z2 M a2 D b2 La x2 The iron alloy powder material mainly composed of is obtained by removing the matrix phase from the initial alloy solid and retaining the dispersed particle phase, so the properties (including particle shape) of the iron alloy powder material correspond to the properties of the dispersed particles in step 2, and details will be described in step 2.

[0102] Furthermore, the method for removing the matrix phase and retaining the dispersed particle phase includes at least one of removal by dissolution reaction with an acid solution and removal by oxidizing and powdering the matrix.

[0103] When removing by acid solution reaction, the appropriate type and concentration of acid should be selected. The selection criteria are mainly La x1 M a1 The matrix phase with an average composition of isopropyl alcohol is dissolved in the solution and is mainly composed of Fe. y2 T z2 M a2 D b2 La x2 The objective is to make the dispersed particle phase with the composition of almost no reaction with the corresponding acid, thereby realizing the removal of the matrix phase, mainly Fe y2 T z2 M a2 D b2 La x2 The iron alloy powder material having the composition of is obtained. Alternatively, the appropriate acid type and concentration are selected, and the selection criteria are mainly La x1 M a1 Matrix phase change nanoporous M (corrodes mainly only La) with an average composition of mainly Fe y2 T z2 M a2 D b2 La x2 The aim is to make the dispersed particle phase with the composition of nanoporous M and Fe almost non-reactive with the corresponding acid. y2 T z2 M a2 D b2 La x2 A composite powder of dispersed particles is obtained.

[0104] When Cr and V are dissolved in Fe, it becomes a ferritic stainless steel component, and Fe y2 T z2 M a2 D b2 La x2 The particle dispersion phase, which is mainly composed of La, has very good corrosion resistance to acids, and the elements La and M react very easily with acid solutions. Therefore, it is very easy to remove the La-rich matrix phase and replace it with Fe. y2 T z2 M a2 D b2 La x2 It is possible to obtain an iron alloy powder material mainly composed of

[0105] Since La is easily oxidized and powdered in air, the La-rich matrix phase can be removed from the initial alloy solid by a dry process in addition to removal by acid solution dissolution reaction. When the La-rich matrix is ​​oxidized and powdered, the Fe-rich dispersed particle phase is automatically detached, and its magnetism can be utilized to recover the Fe-rich particles through a magnetic field to achieve separation from the La-rich matrix phase.

[0106] In addition, the oxidation and powdering process of the La-rich matrix phase in the initial alloy solid is accelerated in the presence of heat treatment, and the La-rich matrix phase is rapidly oxidized and powdered by heat treatment heating, thereby improving the separation efficiency. The addition of elements such as Cr and V improves the oxidation resistance of the Fe-rich particle phase, and the controlled heating temperature prevents the oxidation of the Fe-rich particles.

[0107] Furthermore, the heat treatment temperature is 50°C to 1000°C. Preferably, the heat treatment temperature is 50°C to 600°C. More preferably, the heat treatment temperature is 50°C to 200°C.

[0108] Furthermore, the volume percentage content of spherical or near-spherical iron alloy powder particles among all iron alloy powder particles can approach but not reach 100%, i.e., the iron alloy powder particles are mainly spherical or near-spherical in shape, and some of the spherical or near-spherical iron alloy powder particles contain dendritic features that are insufficiently spheroidized.

[0109] Furthermore, the spherical or nearly spherical iron alloy powder particles have a sphericity of more than 50%.

[0110] Furthermore, the spherical or nearly spherical iron alloy powder particles have a sphericity of more than 70%.

[0111] Furthermore, the spherical or nearly spherical iron alloy powder particles have a sphericity of more than 85%.

[0112] Furthermore, the spherical or nearly spherical iron alloy powder particles have a sphericity of more than 95%.

[0113] Furthermore, the volume percentage content of the spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 10%.

[0114] Furthermore, the volume percentage content of the spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 25%.

[0115] Furthermore, the iron alloy powder particles are primarily spherical or near spherical in shape.

[0116] Furthermore, the volume percentage content of the spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 50%.

[0117] Furthermore, the volume percentage content of the spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 75%.

[0118] Furthermore, the volume percentage content of spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 90%.

[0119] Furthermore, the volume percentage content of spherical or nearly spherical iron alloy powder particles in the total iron alloy powder particles is greater than 95%.

[0120] Generally, when the content of solute T element in the iron alloy powder particles exceeds 2%, or the total content of solute elements including T element exceeds 4%, and the cooling rate of the melt exceeds 500 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 50% of the total iron alloy powder particles.

[0121] Generally, when the content of solute T element in the iron alloy powder particles exceeds 4%, or the total content of solute elements including T element exceeds 8%, and the cooling rate of the melt exceeds 250 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 50% of the total iron alloy powder particles.

[0122] Generally, when the content of solute T element in the iron alloy powder particles exceeds 8%, or the total content of solute elements including T element exceeds 12%, and the cooling rate of the melt exceeds 100 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 50% of the total iron alloy powder particles.

[0123] Generally, when the content of solute T element in the iron alloy powder particles exceeds 12%, or the total content of solute elements including T element exceeds 18%, and the cooling rate of the melt exceeds 50 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 50% of the total iron alloy powder particles.

[0124] Generally, when the content of solute T element in the iron alloy powder particles exceeds 16%, or the total content of solute elements including T element exceeds 25%, and the cooling rate of the melt exceeds 20 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 50% of the total iron alloy powder particles.

[0125] Generally, when the content of solute T element in the iron alloy powder particles exceeds 16%, or the total content of solute elements including T element exceeds 25%, and the cooling rate of the melt exceeds 100 K / s, the volume percentage content of spherical or near-spherical iron alloy powder particles exceeds 95% of the total iron alloy powder particles.

[0126] Furthermore, the partially spherical or nearly spherical iron alloy powder particles include certain dendritic features, which means that the partially spherical or nearly spherical iron alloy powder particles grow short protruding dendrites, giving the entire spherical or nearly spherical iron alloy powder particle a shape similar to that of the "coronavirus" virus (the protruding dendrites growing on the spherical or nearly spherical iron alloy powder particles correspond to the crowns on the sphere of the "coronavirus"). The specific shape of the protruding dendrites is shown in the examples. Although such protruding dendrites that are not sufficiently spheroidized have some effect on the sphericity of the iron alloy powder particles, the sphericity of the iron alloy powder particles from which the protruding dendrites have grown is high, so that even if a part of the spherical or nearly spherical iron alloy powder particles includes the features of short convex dendrites, such particles are still spherical or nearly spherical iron alloy powder particles with high sphericity.

[0127] Furthermore, the iron alloy powder particles are predominantly spherical or near-spherical in shape, and in addition contain a small amount of a typical dendritic grain phase.

[0128] The iron alloy powder particles are mainly spherical or near-spherical in shape, a part of the spherical or near-spherical iron alloy powder particles contain certain dendritic features, and at the same time, the iron alloy powder particles contain a small amount of typical dendritic grain phase. The presence of these two kinds of dendritic shape features is a unique feature of the iron alloy powder particles obtained by the present invention.

[0129] Furthermore, the iron alloy powder particles have a particle size range of 5 nm to 40 μm. Furthermore, the iron alloy powder particles have a particle size range of 5 nm to 30 μm. Furthermore, the iron alloy powder particles have a particle size range of 5 nm to 20 μm. Furthermore, the iron alloy powder particles have a particle size range of 5 nm to 10 μm.

[0130] Furthermore, the particle size of the iron alloy powder particles is in the range of 100 nm to 50 μm.

[0131] Furthermore, the particle size of the iron alloy powder particles is in the range of 250 nm to 50 μm.

[0132] Furthermore, the particle size of the iron alloy powder particles is in the range of 500 nm to 50 μm.

[0133] Furthermore, the particle size of the iron alloy powder particles is in the range of 5 nm to 100 nm.

[0134] Furthermore, the particle size of the iron alloy powder particles is in the range of 5 nm to 50 nm.

[0135] Furthermore, when the average particle size of the iron alloy powder particles is greater than 0.25 μm, the shape of the powder particles is still predominantly spherical.

[0136] Furthermore, when the average particle size of the iron alloy powder particles is greater than 0.5 μm, the shape of the powder particles is still mainly spherical.

[0137] Furthermore, when the average particle size of the iron alloy powder particles is greater than 1 μm, the shape of the powder particles is still predominantly spherical.

[0138] Furthermore, when the average particle size of the iron alloy powder particles is greater than 3 μm, the shape of the powder particles is still mainly spherical.

[0139] Furthermore, the number of single crystal particles in the iron alloy powder particles accounts for 60% or more of the total number of particles.

[0140] La is a special case among all rare earth elements, and Fe is also a special case among all iron-based elements Fe, Co, and Ni. Among the many combinations of iron-based elements and rare earth elements, only La-Fe alloys do not form intermetallic compounds, and the two elements do not solidify significantly with each other. Utilizing this feature is the basis for forming La-rich matrix phase and Fe-rich dispersed particle phase in the solidification structure of the initial alloy solid of the present invention. Based on this, by selecting and controlling the content of T element, M element, and D element, the growth pattern of the original dendritic particle phase in the solidification process of the initial alloy melt can be changed to a spherical or nearly spherical particle phase, and an ultrafine spherical iron alloy powder can be obtained that has a composition almost similar to that of a general commercial alloy, but has a significantly different particle size (for example, small particle size, low oxygen impurity, rare earth element solid solution, etc.), which is the key to the ingenuity of the present invention. If one does not select and control the content of T, M and D elements, and does not discover and utilize the spherical effect of T element, but merely obtains dendritic and corrodible Fe dendritic powder through La-Fe alloy, there will be no particle mobility and the powder metallurgy will have low density, which will greatly limit the application value.

[0141] In reality, as a rare earth element raw material, La raw material may also contain a small amount of other rare earth elements, but as long as the atomic percentage content of other rare earth elements does not exceed 25% of the content of La raw material, it has little effect on the rule. These other rare earth elements are solid-dissolved in La and replace part of the role of La. At this point, the meaning of La in this invention refers to La rare earth and other rare earths.

[0142] Furthermore, the composition of the initial alloy melt in Step 1 includes non-metallic impurity elements, and at least one of O, N, H, P, S, and Cl is included in the non-metallic impurity elements. The atomic percentage content of the non-metallic impurity elements in the initial alloy melt is greater than 0 and less than 10%. During the formation of the Fe-rich dispersed particle phase in Step 2, the non-metallic impurity elements are enriched in the La-rich matrix phase, thereby purifying the Fe-rich dispersed particle phase. That is, the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is lower than the atomic percentage content of the non-metallic impurity elements in the initial alloy melt, and the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is less than 1.5%. Also, the content of the non-metallic impurity elements in the spherical or near-spherical iron alloy powder particles in Step 3 is also lower than the content of the non-metallic impurity elements in the initial alloy melt.

[0143] Furthermore, the obtained iron alloy powder particles are subjected to particle size classification to separate them into powders of 10 μm or more, powders of 1 μm to 5 μm, powders of 5 μm to 10 μm, powders of 1 μm or less, etc., and spherical iron alloy powder materials with different particle sizes are obtained, which can be applied to various fields.

[0144] Second aspect, the present invention also relates to a spherical iron alloy powder material characterized by being manufactured by the method for manufacturing a spherical iron alloy powder material described in the first aspect thereof. The features are described in detail in the first aspect.

[0145] Some of the features of the spherical iron alloy powder material include: the main composition of the spherical iron alloy powder material is Fe y2 T z2 M a2 D b2 La x2 where 50% ≦ y2 ≦ 98%, 0.2% ≦ z2 < 50%, 0% ≦ a2 ≦ 30%, 0% ≦ b2 ≦ 35%, and 0 < x2 ≦ 5%. The iron alloy powder particles are mainly spherical or near-spherical in shape, and some of the spherical or near-spherical iron alloy powder particles include specific dendritic characteristics, and the particle size range of the iron alloy powder particles is 5 nm to 50 μm.

[0146] Furthermore, the spherical or nearly spherical iron alloy powder particles have a sphericity of more than 65%.

[0147] Furthermore, the volume percentage content of the nearly spherical iron alloy powder particles in the total iron alloy powder is greater than 25%.

[0148] Furthermore, the near-spherical iron alloy powder particles have a total atomic percentage content of the elements O, N, H, P, S, and Cl of less than 1.5%.

[0149] Furthermore, the above T includes at least one of Cr and V, M includes at least one of Al, Ni, Co, and Si, D includes at least one of Mo, W, and Ti, and x1, a1, x2, y2, z2, a2, and b2 each represent the atomic content of the corresponding constituent element.

[0150] In a third aspect, the present invention also relates to a method for producing a spherical iron-chromium-silicon powder material with a high Si content, which is characterized in that a spherical iron alloy powder material whose main component element is Fe-Cr, or a spherical iron alloy powder material whose main component element is Fe-Cr-Si and has a low Si content, produced in steps 1 to 3 described in the first aspect, is subjected to a Si infiltration treatment to obtain a spherical powder material whose main component element is Fe-Cr-Si and has a high Si content.

[0151] The solid solubility of the atomic percentage of Si in the Fe-Cr-Si spherical iron alloy powder material directly obtained by steps 1 to 3 described in the first embodiment is difficult to exceed 8%, and can be achieved only when the initial alloy melt contains a large amount of Si. On the other hand, the atomic percentage of Si in Fe-Cr-Si magnetic iron alloy powder actually available on the market generally needs to be 8% or more. In order to obtain a higher Si content, a spherical Fe-Cr-Si powder material with a high Si content can be obtained by subjecting the spherical iron alloy powder material with Fe-Cr as the main component element produced by steps 1 to 3 described in the first embodiment or the spherical iron alloy powder material with Fe-Cr-Si as the main component element and a low Si content to Si infiltration treatment.

[0152] Furthermore, the Si infiltration treatment includes at least one of a solid Si infiltration, a liquid Si infiltration, and a gas Si infiltration process.

[0153] Furthermore, the silicon source for solid Si infiltration includes at least one of Si or an Si-rich alloy, the silicon source for liquid Si infiltration is mainly an Si-containing liquid, and the silicon source for gas Si infiltration is mainly an Si-containing gas.

[0154] Furthermore, the processing temperature of the solid Si infiltration is 400°C to 1200°C.

[0155] Furthermore, the present invention also provides an improved Si infiltration treatment process.

[0156] Furthermore, according to Step 1 and Step 2 of the first aspect, the initial alloy solid described in Step 2 of the first aspect is manufactured. Here, T contains Cr, M contains Si, and 0 < a ≤ 40%. The average composition of the matrix phase is mainly La x1 Si a1 and the composition of the dispersed particle phase is mainly Fe with a low Si content y2 Cr z2 Si a2 D b2 La x2 wherein the Si in the La x1 Si a1 matrix phase is combined with La by an intermetallic compound, and 0 < a2 ≤ 8%. The initial alloy solid La x1 Si a1 the La in the matrix phase is removed by a dealloying reaction with a dilute acid solution while retaining the original La x1 Si a1 Si in the matrix phase, and a composite powder of nanoporous Si and the above Fe with a low Si content y2 Crz2Si a2 D b2 La x2 particles is obtained. The above nanoporous Si is Fe y2 Cr z2 Si a2 D b2 La x2It can be used as a Si source for infiltrating Si into powders.

[0157] Furthermore, the above nanoporous Si was used as a Si source to synthesize Fe with a low Si content. y2 Cr z2 S a2 D b2 La x2 The particles are infiltrated with Si, thereby obtaining spherical Fe-Cr-Si powder material with high Si content.

[0158] In addition, nanoporous Si and Fe with low Si content y2 Cr z2 S a2 D b2 La x2 The solid Si infiltration method of the particles includes directly carrying out solid Si infiltration, or first pressing to densify, and then carrying out solid Si infiltration operation.

[0159] Furthermore, the processing temperature for solid Si infiltration is 400°C to 1200°C.

[0160] Furthermore, the composition of the obtained spherical Fe-Cr-Si powder material with a high Si content is mainly Fe y3 Cr z3 S a3 D b3 La x3 where x3, y3, z3, a3, and b3 each represent the atomic percentage content of the corresponding constituent element, and are 0 <y3<y2、0<z3<z2、0<a2<a3、0≦b3≦b2、0<x3<x2である。

[0161] Additionally, 5% <a3である。さらに、10%<a3である。

[0162] Furthermore, the morphology and size of the spherical Fe-Cr-Si powder material with high Si content are basically the same as before the infiltration treatment, except that the Si content is increased by the infiltration treatment and the alloy composition is automatically adjusted accordingly.

[0163] In addition, because Si is brittle, the spherical Fe-Cr-Si powder material with high Si content after silicon infiltration treatment can be re-ground into loose particles by dispersion and grinding techniques. There may be residual nanoporous Si that is not completely infiltrated on the surface of the spherical Fe-Cr-Si powder with high Si content, which can be beneficially present.

[0164] Furthermore, the obtained spherical Fe-Cr-Si powder particles with a high Si content are subjected to particle size classification to separate them into powders of 10 μm or more, powders of 1 μm to 5 μm, powders of 5 μm to 10 μm, and powders of 1 μm or less, etc., to obtain spherical Fe-Cr-Si powder materials with a high Si content of different particle sizes, which can be applied to various fields.

[0165] In a fourth aspect, the present invention also relates to a spherical iron-chromium-silicon powder material with a high Si content, which is produced by the method for producing a spherical iron-chromium-silicon powder material with a high Si content described in the third aspect, the characteristics of which are described in detail in the third aspect.

[0166] In a fifth aspect, the present invention also provides nanoporous Si and Fe with low Si content by the improved silicon infiltration process described in the third aspect. y2 Cr z2 S a2 D b2 La x2 and obtaining a composite powder of nanoporous Si and spherical Fe-Cr-Si particles, the characteristics of which are described in the improved silicon infiltration process of the third aspect.

[0167] In a sixth aspect, the present invention also provides a method for producing an iron-chromium-nickel powder metallurgy product having a high nickel content, the method comprising the steps of:

[0168] Process 1: According to Process 1 and Process 2 of the first aspect, produce the initial alloy solid described in Process 2 of the first aspect. Here, T contains Cr, M contains Ni, and 0 < a ≤ 40%. The average composition of the matrix phase is mainly La x1 Ni a1 and the composition of the dispersed particle phase is mainly Fe with a low Ni content y2 Cr z2 Ni a2 D b2 La x2 and the Ni in the La x1 Ni a1 matrix phase is combined with La by an intermetallic compound, and 0 < a2 ≤ 12%.

[0169] Process 2: While preventing most of the Ni in the La x1 Ni a1 matrix phase from being removed by reaction, remove it by a dealloying reaction with a dilute acid solution to obtain a composite powder of nanoporous Ni and Fe x1 Ni a1 with a low Ni content, Cr y2 Cr z2 Ni a2 D b2 La x2 particles.

[0170] Process 3: Press and mold the composite powder of nanoporous Ni and the Fe y2 Cr z2 Ni a2 D b2 La x2 particles, and perform heat treatment and sintering to obtain an FeCrNi powder metallurgy product with a high Ni content in the main component composition y3 Cr z3 Ni a3 D b3 La x3 . Here, x3, y3, z3, a3, and b3 represent the atomic percentage contents of the corresponding constituent elements, respectively, and 0 < y3 < y2, 0 < z3 < z2, 0 < a2 < a3, 0 ≤ b3 ≤ b2, and 0 < x3 < x2.

[0171] During the solidification of the initial alloy melt according to the first embodiment, the Ni element in the matrix is ​​enriched, so the atomic percentage of Ni in the Fe-rich phase dispersion particles generally does not exceed 12%. Generally, the Ni content in Fe-Ni high temperature alloys must be 30%-40%, so the Fe-Ni alloy with a low Ni content can be obtained by the method of the present invention. y2 Cr z2 Ni a2 D b2 La x2 By increasing the Ni content in the particles, it is possible to obtain FeCrNi powder metallurgy products with high Ni content, which are suitable for high temperature alloy fields.

[0172] In the above step 1, Furthermore, 18%≦x≦85%, 10%≦y≦81.8%, 5%≦a≦40%, 2%≦z≦35%, 0%≦b≦15%, 45%≦x1≦100%, 0%≦a1≦55%, 50%≦y2≦85%, and 4%≦z2<50%.

[0173] Furthermore, the above La x1 Ni a1 The method in which Ni in the matrix phase is bonded to La via an intermetallic compound includes at least one of a La3Ni intermetallic compound, a La7Ni3 intermetallic compound, and a LaNi intermetallic compound.

[0174] In the above step 2, Both La and Ni can react with acid, but the reactivity of the rare earth La is high, and intermetallic compounds generally have a high La content. Therefore, by adjusting the type and concentration of dilute acid, La is corroded and removed by dealloying reaction, and a small amount of Ni is inevitably corroded and dissolved, but most of the Ni can be retained in the nanoporous Ni by the dealloying reaction. On the other hand, Fe with a low Ni content y2 Cr z2 Ni a2 D b2 La x2 The grain phase contains Cr, has excellent corrosion resistance and can be completely retained.

[0175] Moreover, the size of the nanoporous Ni strips is less than 200 nm.

[0176] After the dealloying reaction of the present invention, the nanoporous Ni is significantly fragmented and cannot be retained as an intact matrix, so the resulting nanoporous Ni and Fe with a low Ni content are y2 Cr z2 Ni a2 D b2 La x2 Fe with low Ni content in composite powder with particles y2 Cr z2 Ni a2 D b2 La x2 The particles are freely separated and only mixed with the nanoporous Ni fragments.

[0177] In the above step 3, Furthermore, the press molding and the heat treatment sintering may be carried out sequentially or simultaneously, and simultaneous hot press sintering is used.

[0178] Furthermore, the above heat treatment sintering temperature is the same as that of Fe with a low Ni content. y2 Cr z2 Ni a2 D b2 La x2 It is below the melting point of the particles.

[0179] Furthermore, the heat treatment sintering temperature is 400°C to 1400°C.

[0180] Furthermore, the heat treatment sintering temperature is 400°C to 1100°C.

[0181] Furthermore, the heat treatment sintering temperature is 400°C to 900°C.

[0182] Furthermore, in the above heat treatment sintering process, the nanoporous Ni has a low Ni content of Fe y2 Cr z2 Ni a2 D b2 La x2 It penetrates into the grains and dissolves therein, resulting in an increase in the Ni content.

[0183] Additionally, 10% <a3である。さらに、15%<a3である。さらに、20%<a3である。さらに、30%<a3である。

[0184] In a seventh aspect, the present invention also relates to an iron-chromium-nickel powder metallurgy product with a high nickel content, characterized in that it is produced by the method for producing an iron-chromium-nickel powder metallurgy product with a high nickel content according to the sixth aspect thereof, the characteristics of which are described in detail in the sixth aspect.

[0185] In an eighth aspect, the present invention also relates to a composite powder of nanoporous Ni and Fe-Cr-Ni particles with low Ni content, characterized in that it is produced by steps 1 and 2 of the sixth aspect thereof, the characteristics of which are described in detail in the sixth aspect.

[0186] In a ninth aspect, the present invention also relates to the use of the spherical iron alloy powder material according to the second aspect in any of the fields of conventional powder metallurgy, metal injection molding (MIM), 3D printing, magnetic materials, heat-resistant materials, high-temperature alloys, paints, wave absorbing materials, etc.

[0187] The spherical iron alloy powder material according to the first and second aspects of the present invention can be used in the general field of powder metallurgy, i.e., by compressing the powder into a compact and then sintering it to produce a bulk powder metallurgy product of a corresponding composition, or by mixing the powder with other powders, compressing the powder into a compact and then sintering it to produce a bulk powder metallurgy product of a corresponding composition. The other powders include at least one of metal powders, alloy powders, oxide powders, carbide powders, nitride powders, carbon powders, and ceramic powders.

[0188] In the field of metal injection molding (MIM), the theoretical optimum particle size of powder material for MIM is 0.5 μm to 10 μm, but due to current technical limitations, the particle size of powder material used for MIM is generally 10 μm or more, or even 50 μm or more. The method described in the present invention is very suitable for producing powder with a particle size of 0.5 μm to 10 μm, and the finer the powder, the easier it is to produce. Therefore, the iron alloy powder material involved in the first and second aspects of the present invention is very suitable for use in the field of metal injection molding (MIM). The difference between MIM technology and ordinary powder metallurgy technology is that MIM is carried out by using powder and an organic binder to create a compact, removing the organic binder, and then sintering to obtain a product, and due to the removal of the binder, the sintered product shrinks by 10% to 20% relative to the volume of the compact.

[0189] In the field of 3D printing, in order to 3D print fine lay-up powder, spherical powder with a particle size of about 15 μm to 53 μm is required. In the present invention, when the content of elements dissolved in Fe is very high and the content of Cr and V is very high, a spherical iron alloy powder in this particle size range can be obtained, and the powder in this particle size range can be concentrated by further sieving. Therefore, the spherical iron alloy powder material according to the first and second aspects of the present invention can also be used in the field of 3D printing in some cases.

[0190] In the field of magnetic materials, the spherical iron alloy powder materials according to the first and second aspects of the present invention can be used for soft magnetic materials and hard magnetic materials (permanent magnets). For example, powder materials mainly composed of Fe-Cr and Fe-Cr-Si can be used for soft magnetic materials (e.g., dust cores), and powder materials mainly composed of Fe-Cr-Co can be used for hard magnetic materials.

[0191] Furthermore, when the powder material containing Fe-Cr and Fe-Cr-Si as main components according to the present invention is used as a soft magnetic material, it can also be used as a dust core.

[0192] The dust core is manufactured by applying an insulating coating material to a powder material mainly composed of Fe-Cr and Fe-Cr-Si, and then pressing the powder material at a constant temperature, the pressing temperature being from room temperature to 800°C.

[0193] Furthermore, the weight percentage of the insulating coating material in the powder magnetic core is more than 0.1% and less than 15%.

[0194] Furthermore, the insulating coating material includes a resin, and preferably includes at least one of a silicone resin, a phenolic resin, an epoxy resin, a polypropylene, and a nylon.

[0195] In the field of heat-resistant materials, the powder materials or powder metallurgy products or MIM products manufactured from the spherical iron alloy powder materials containing high melting point elements such as V, W, Mo, Ti, etc. according to the first and second aspects of the present invention, or the spherical iron alloy powder materials containing Al and capable of forming alumina at high temperatures, for example, the spherical iron alloy powder materials mainly composed of Fe-Cr-Al, Fe-Cr-Al-(V / W / Mo / Ti), can greatly improve heat-resistant properties and can be used as heat-resistant materials. In various aspects of industrial applications such as heating furnaces, heat exchangers, fiber burners, and high-temperature gas filtration systems, especially as metal honeycomb carriers for exhaust gas catalysts, iron-chromium-aluminum metallurgy alloy products have obvious advantages over traditional ceramic honeycomb carriers.

[0196] In the field of high-temperature alloys, products manufactured from the spherical iron alloy powder material containing high-melting point elements such as V, W, Mo, Ti according to the first and second aspects of the present invention, for example, the spherical iron alloy powder material mainly composed of Fe-Cr-Ni-(V / W / Mo / Ti), have excellent high-temperature resistance. When the composition of the spherical iron alloy powder material containing high-melting point elements such as V, W, Mo, Ti according to the first and second aspects of the present invention is the same as or close to the composition of the high-temperature alloy, it can be used in the field of high-temperature alloys.

[0197] In the field of paints, the spherical iron alloy powder materials according to the first and second aspects of the present invention can be used as a main component in the field of paints including thermal spray paints, resin-based paints, and magnetic shielding paints.

[0198] In the field of wave absorbing materials, the spherical iron alloy powder material according to the first and second aspects of the present invention can be used as a magnetic metal powder in the field of wave absorbing materials.

[0199] In a tenth aspect, the present invention also relates to the use of the spherical iron alloy powder material according to the second aspect in the field of electric heating materials. The spherical iron alloy powder material is mainly composed of Fe-Cr-Al.

[0200] In the field of electric heating materials, the powder materials mainly composed of Fe-Cr-Al and Fe-Cr-Al-(V / W / Mo / Ti) according to the first and second aspects of the present invention become excellent electric heating materials when they are manufactured by powder metallurgy technology. For example, the iron-chromium-aluminum electric heating alloy element manufactured from the powder materials mainly composed of Fe-Cr-Al and Fe-Cr-Al-(V / W / Mo / Ti) can reach a service temperature of 1400°C or higher. The alloy mainly composed of Fe-Cr-Al has a high aluminum content, so that the resistivity is high, and the maximum value reaches 1.6μΩ·m. The high resistivity allows the electric energy to be effectively converted into thermal energy. At the same time, the price of the iron-chromium-aluminum alloy is low, only 20%-25% of that of the nickel-chromium alloy, so the conditions for its mass use are in place. In addition, it has good heat resistance, low specific gravity, and excellent resistance to high-temperature oxidation, so it is widely used in all aspects of production and life. For example, in the field of daily life, the heating elements that FeCrAl powder metallurgy alloys are applied to include electric stove wires, electric stove rods, cooking plates, radiators, toasters, microwave ovens, water heaters, washing machines, boilers, precision resistor elements in automobiles, etc.

[0201] In an eleventh aspect, the present invention also relates to the use of the spherical iron-chromium-silicon powder material having a high Si content according to the fourth aspect in a magnetic material.

[0202] Furthermore, when the spherical iron-chromium-silicon powder material having a high Si content according to the fourth aspect of the present invention is used as a soft magnetic material, it can also be used as a dust core.

[0203] The dust core is manufactured by applying an insulating coating material to a spherical iron-chromium-silicon powder material having a high Si content, and then pressing the powder at a constant temperature, the pressing temperature being from room temperature to 800°C.

[0204] Furthermore, the weight percentage of the insulating coating material in the powder magnetic core is more than 0.1% and less than 15%.

[0205] Furthermore, the insulating coating material includes a resin, and preferably includes at least one of a silicone resin, a phenolic resin, an epoxy resin, a polypropylene, and a nylon.

[0206] In a twelfth aspect, the present invention also relates to the use of the high Ni iron-chromium-nickel powder metallurgy product according to the seventh aspect in a high temperature alloy.

[0207] The high temperature alloy mainly includes nickel-based high temperature alloy, iron-based high temperature alloy, and nickel-iron-based high temperature alloy. When the composition of the high Ni content iron-chromium-nickel powder metallurgy product according to the seventh aspect of the present invention is the same as or close to the composition of the high temperature alloy, it can be used in the field of high temperature alloy.

[0208] In a thirteenth aspect, the present invention also relates to an alloy solid, characterized in that it is produced by the method for producing an initial alloy solid according to steps 1 and 2 of the first aspect, the characteristics of which are described in detail in the first aspect.

[0209] Its specific features include that it is manufactured by the following steps.

[0210] Step 1: Select an initial alloy raw material, melt the initial alloy raw material according to the initial alloy composition ratio, and obtain a homogeneous initial alloy melt. The main component of the initial alloy melt is La.x Fe y T z M a D b wherein T contains at least one of Cr and V, M contains at least one of Al, Ni, Co, and Si, and D contains at least one of Mo, W, and Ti. x, y, z, a, and b represent the atomic percentage contents of the corresponding constituent elements, and 18% ≤ x ≤ 95.8%, 4% ≤ y ≤ 81.8%, 0.1% ≤ z ≤ 35%, 0 ≤ a ≤ 40%, and 0 ≤ b ≤ 15%.

[0211] Step 2: Solidify the above initial alloy melt into an initial alloy solid by a rapid solidification method. The solidification structure of the above initial alloy solid includes a matrix phase and a dispersed particle phase. The matrix phase has a melting point lower than that of the dispersed particle phase. The dispersed particle phase is encapsulated in the matrix phase, and the volume percentage content of the matrix phase in the solidification structure is 40% or more. The average composition of the matrix phase is mainly La x1 M a1 wherein the composition of the dispersed particle phase is mainly Fe y2 T z2 M a2 D b2 La x2 wherein x1, a1, x2, y2, z2, a2, and b2 represent the atomic percentage contents of the corresponding constituent elements, and 45% ≤ x1 ≤ 100%, 0% ≤ a1 ≤ 55%, 50% ≤ y2 ≤ 98%, 0.2% ≤ z2 < 50%, 0% ≤ a2 ≤ 30%, 0% ≤ b2 ≤ 35%, and 0 < x2 ≤ 5%. The dispersed particle phase contains a considerable amount of spherical or nearly spherical dispersed particle phases. A part of the spherical or nearly spherical dispersed particle phases contains specific dendritic features, and the particle size of the dispersed particle phase is 5 nm to 50 μm.

[0212] Furthermore, the composition of the initial alloy melt in Step 1 includes non-metallic impurity elements, and at least one of O, N, H, P, S, and Cl is included in the non-metallic impurity elements. The atomic percentage content of the non-metallic impurity elements in the initial alloy melt is greater than 0 and less than 10%. During the formation of the Fe-rich dispersed particle phase in Step 2, the non-metallic impurity elements are enriched in the La-rich matrix phase, thereby purifying the Fe-rich dispersed particle phase. That is, the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is lower than the atomic percentage content of the non-metallic impurity elements in the initial alloy melt, and the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is less than 1.5%.

[0213] A 14th aspect, the present invention also relates to the use of the spherical iron alloy powder material described in the second aspect in the field of magnetic fluids.

[0214] The characteristics of the spherical iron alloy powder material are described in detail in its first aspect and second aspect. Examples of the characteristics of the spherical iron alloy powder material include: The main component of the spherical iron alloy powder material is Fe y2 T z2 M a2 D b2 La x2 where 50% ≦ y2 ≦ 98%, 0.2% ≦ z2 < 50%, 0% ≦ a2 ≦ 30%, 0% ≦ b2 ≦ 35%, 0 < x2 ≦ 5%. The spherical iron powder particles are mainly spherical or nearly spherical in shape, and some of the spherical or nearly spherical iron alloy powder particles include specific dendritic features. The particle size of the iron alloy powder particles is 5 nm to 100 nm, T includes at least one of Cr and V, M includes at least one of Al, Ni, Co, and Si, and D includes Mo, W, and Ti. x1, a1, x2, y2, z2, a2, b2 represent the atomic content percentages of the corresponding constituent elements respectively.

[0215] Preferably, the particle size range of the spherical iron alloy powder particles is 5 nm to 50 nm.

[0216] More preferably, the particle size of the spherical iron alloy powder particles is in the range of 5 nm to 25 nm.

[0217] Furthermore, 50%≦y2≦95%.

[0218] Furthermore, 1%≦z2+b2<50%. Furthermore, 2%≦z2+b2<50%. Furthermore, 3%≦z2+b2<50%.

[0219] Furthermore, 1%≦z2<50%. Furthermore, 2%≦z2<50%. Furthermore, 3%≦z2<50%.

[0220] The iron alloy powder particles according to the first and second aspects of the present invention can be used in the field of magnetic fluids, specifically by mixing the iron alloy powder particles with a carrier fluid and a surfactant to obtain a magnetic fluid.

[0221] Additionally, the carrier fluid includes at least one of water, ethanol, carbohydrates, fats, dibasic fats, and mercury.

[0222] Further, the surfactant includes at least one of oleic acid, polyvinylpyrrolidone, polyethylene glycol, ethylene glycol, and sodium dodecylbenzenesulfonate.

[0223] As magnetic solid particles for magnetic fluids, their particle size is generally required to be on the nanoscale. Although Fe is one of the most excellent magnetic materials, when using nano-Fe particles as magnetic solid particles for magnetic fluids, the nano-Fe particles are very easily oxidized, resulting in unstable performance and difficulty in proper application. The present invention can well solve this problem when the solid solution of the produced spherical Fe alloy powder particles contains a certain amount of corrosion-resistant elements such as Cr, V, Mo, W, and Ti. It not only makes the spheroidization clearer but also significantly improves the corrosion resistance of the nano-Fe alloy powder particles. Due to this improvement in corrosion resistance, it becomes possible to remove the matrix in the alloy as a solid with an acid corrosion solution while retaining the nano-Fe alloy powder particles, and at the same time, it becomes possible to apply the corrosion-resistant nano-Fe alloy powder particles as magnetic solid particles for magnetic fluids.

[0224] A 15th aspect, the present invention also relates to spherical iron alloy powder particles in the shape of a coronavirus, including the following features. The main component of the spherical iron alloy powder particles in the shape of the coronavirus is Fe y2 T z2 M a2 D b2 La x2 where 50% ≤ y2 ≤ 98%, 0.2% ≤ z2 < 50%, 0% ≤ a2 ≤ 30%, 0% ≤ b2 ≤ 35%, and 0 < x2 ≤ 5%, T includes at least one of Cr and V, M includes at least one of Al, Ni, Co, and Si, D includes at least one of Mo, W, and Ti, La is rare earth La, and La is mainly Fe y2 T z2 M a2 D b2 La x2The coronavirus-shaped spherical iron alloy powder particles have a main component of x1, a1, x2, y2, z2, a2, and b2, and are present in a solid solution in the coronavirus-shaped spherical iron alloy powder particles, where x1, a1, x2, y2, z2, a2, and b2 respectively represent the atomic percentage contents of the corresponding constituent elements. The coronavirus-shaped spherical iron alloy powder particles include a main body portion and an appendage portion, the main body portion being a sphere or a sphere close to a sphere, and the appendage portion being a plurality of protrusions grown in situ on the surface of the sphere of the main body portion, the spherical iron alloy powder particles have a shape similar to a coronavirus, and the plurality of protrusions of the appendage portion correspond to the plurality of crown protrusions of the coronavirus shape. The diameter of the main body portion of the coronavirus-shaped spherical iron alloy powder particles is 20 nm to 50 μm, and the height of the protrusions of the appendage portion is less than 0.3 times the diameter of the sphere of the main body portion.

[0225] Furthermore, the number of protrusions on the single coronavirus-shaped spherical iron alloy powder particle is more than five.

[0226] Furthermore, the number of protrusions on the single coronavirus-shaped spherical iron alloy powder particle is more than 10.

[0227] Furthermore, the diameter range of the main body sphere of the above coronavirus-shaped spherical iron alloy powder particles is 50 nm to 15 μm.

[0228] Furthermore, the diameter range of the main body part sphere of the above coronavirus-shaped spherical iron alloy powder particles is 200 nm to 10 μm.

[0229] Furthermore, the diameter range of the main body part sphere of the above coronavirus-shaped spherical iron alloy powder particles is 200 nm to 5 μm.

[0230] Furthermore, any single protrusion of said appendage is comprised of no more than one crystal grain, the crystal structure and crystal plane orientation of which is the same as the crystal structure and crystal plane orientation of the spherical portion to which it is connected.

[0231] Furthermore, both the main body and the accessory parts of the coronavirus-shaped spherical iron alloy powder particles belong to a large single crystal.

[0232] It can be understood that the crystal structure and crystal plane orientation at the junction between the main body and the appendage are consistent in both the main body and the appendage. Therefore, it is believed that the main body sphere and the multiple appendage irregularities of the coronavirus-shaped spherical iron alloy powder particle belong to one large single crystal.

[0233] Furthermore, the height of the protrusion of the appendage is less than 0.2 times the diameter of the main body sphere.

[0234] Furthermore, the protrusions are dendrites. That is, the protrusions are preferential growth points for the transition from a spherical particle to a dendritic particle. Alternatively, it can be understood that after a spherical particle grows to a certain stage, a preferential growth point appears at a certain part of the spherical surface, and the growth point continues to grow preferentially as a protrusion according to the original crystal structure and crystal plane orientation of the growth point.

[0235] Furthermore, the diameter of the appendage of the protrusion is less than 0.25 times the diameter of the main sphere of the coronavirus-shaped spherical iron alloy powder particle.

[0236] Furthermore, the morphological characteristics of the above coronavirus-shaped spherical iron alloy powder particles can refer to the shapes of the coronavirus-shaped spherical particles shown in Figures 3, 11, 12, and 15 in the embodiments.

[0237] Furthermore, the coronavirus-shaped spherical iron alloy powder material is produced by the method according to the first aspect thereof.

[0238] Specifically, the present invention has the following beneficial effects:

[0239] First, the precipitation and subsequent separation of the corrosion-resistant, oxidation-resistant spherical or nearly spherical Fe-rich dispersoid phase in the La-rich matrix phase is achieved by the addition design of the T element. The selection of the T element has several original features. The T element is completely miscible with Fe and can be added in large quantities. Like Fe, the T element does not form intermetallic compounds with La, hardly penetrates into the La-rich phase, and only penetrates into the Fe-rich dispersoid phase. When the T element is present in solid solution, the Fe-rich dispersoid phase tends to become spherical, which is the key to producing spherical or nearly spherical Fe alloy powder. The T element and the D element are completely miscible, and when the solid solubility of the D element in Fe is 10-20%, the presence of the T element allows the Fe-rich dispersoid phase to more readily dissolve more D element. The T elements Cr and V are corrosion-resistant elements in Fe alloys. By entering the Fe-rich dispersed particle phase, the corrosion resistance and oxidation resistance of the Fe-rich dispersed particle phase can be greatly improved, and the Fe-rich dispersed particle phase can be separated from the La-rich matrix phase by acid corrosion reaction and oxidation powder separation. Otherwise, the simple Fe phase is also easily reacted with acid and oxidized, especially when the particle phase is relatively small.

[0240] Second, the spherical or nearly spherical Fe alloy powder has beneficial rare earth elements directly dissolved in it. The addition of rare earth elements in the Fe alloy has a positive effect on the performance of the material. For example, adding a small amount of rare earth elements to an Fe-Cr-Al electric heating alloy improves the performance of the electric heating alloy. In industry, rare earth elements are added to Fe alloys, but because rare earth elements are easily oxidized, when a small amount of rare earth elements is added, the rare earth elements generally combine with impurities such as oxygen in the alloy and exist unevenly in the alloy in the form of oxide particles, so there is a limit to improving the performance of the alloy. However, since the initial alloy melt of the present invention contains a large amount of La (the volume percentage content of the La-rich matrix phase is 40% or more), the oxygen in the alloy melt is mainly present in the La-rich matrix phase, and a small amount of La is dissolved in the spherical or nearly spherical Fe alloy powder. This La is homogeneously dissolved in the Fe alloy powder in the atomic state, and is a strictly alloyed rare earth element, which has a better effect on the properties of the material. The presence of a rare earth element (La) in solid solution in the Fe alloy powder is one of the important features of the iron alloy powder material produced by the present invention.

[0241] Third, the present invention realizes the production of ultrafine Fe alloy powder material mainly composed of spherical or nearly spherical particles. Spherical or nearly spherical Fe alloy particles have excellent fluidity, homogeneity, and dense powder lamination, and are therefore the main raw material for applications such as powder metallurgy, powder spraying, powder coating, metal injection molding (MIM), and 3D printing. Currently, spherical Fe alloy powder material cannot be produced by chemical methods, and can only be produced by the atomization method, that is, by directly pulverizing liquid metal or alloy with high-speed fluid to obtain metal powder. However, due to the limitations of the atomization ability of the atomization method, it is generally only suitable for producing spherical Fe alloy powder of 10 μm to 150 μm. For spherical Fe alloy powder material of 10 μm or less, especially around 1 μm, it is difficult or impossible to produce it by the atomization method. The technical solution provided by the present invention achieves the production of ultrafine spherical Fe alloy powder materials with particle sizes from nanoscale to several microns, and such ultrafine spherical Fe alloy powder materials can be obtained on a large scale and at low cost, which has obvious positive significance in terms of application.

[0242] Fourth, some of the produced spherical or nearly spherical iron alloy powder particles contain convex short dendritic characteristics. In powder metallurgy, especially MIM, the strength of the crude product is one of the important factors in normal production. For example, MIM blank products by metal injection molding are obtained by pressing metal powder and organic binder and removing the organic binder. MIM blank products become high-strength products due to shrinkage during sintering, and after removing the organic binder and before sintering, the shape of the MIM blank product must be maintained by relying on the mechanical bond between particles. If the metal powder is all ideal spherical particles, the mechanical frictional bond between the ideal spherical particles is very weak, and the blank product is prone to collapse. In the present invention, some of the spherical or nearly spherical iron alloy powder particles have convex short dendritic characteristics, and this characteristic has little effect on the sphericity of the particles, but can greatly improve the mechanical bond or friction between the particles, thereby increasing the strength of the blank product. If all the particles have this convex short dendritic characteristic, it will affect the powder flowability of the spherical particles. The iron alloy powder particles produced by the present invention are suitable in that this convex short dendritic characteristic appears only on the surface of some of the spherical or near-spherical iron alloy powder particles produced. Therefore, the protruding short dendrites on some of the spherical iron alloy powder particles are another important feature of the Fe alloy powder produced by the present invention.

[0243] Fifth, during the formation of the Fe-rich dispersed particle phase, the Fe-rich dispersed particle phase is refined at the same time. If the initial alloy is produced from raw materials containing impurity elements such as O, N, H, P, S, Cl, or raw materials of lower purity, or if the above impurities are mixed into the molten material during the production of the initial alloy, it does not affect the final production of the Fe-rich dispersed particle phase with a low content of the above impurities, and furthermore, a spherical iron alloy powder material with a low content of the above impurities can be obtained. This is because most of the above impurity elements in the raw materials or the above impurity elements introduced into the molten material during the initial solidification process of the alloy melt are captured by the La-rich matrix phase and then penetrate into the matrix phase, thereby refining the Fe-rich dispersed particle phase.

[0244] Sixth, an iron alloy powder material mainly composed of single crystal particles can be obtained. Compared with polycrystalline powder, single crystal powder can have many important and beneficial effects. During the solidification process of the initial alloy melt, each endogenous particle nucleates from a specific position in the melt and grows according to a specific atomic arrangement. By controlling the volume percentage content of the matrix phase and ensuring the dispersion of each endogenous particle, it is difficult for each endogenous dispersed particle to bond or entangle with each other. As a result, each Fe-rich dispersed particle phase obtained is generally a single crystal phase. In addition, even if a convex short dendrite further grows on a spherical particle, it grows according to a certain crystal direction on the spherical particle surface. That is, the spherical particle and the convex short dendrite become one crystal grain. In the case of polycrystalline materials, their grain boundaries are generally prone to contain impurity elements that are expelled out of the crystal during solidification, making it difficult to obtain high-purity polycrystalline powder materials. In addition, when the powder material is mainly composed of single crystal particles, its purity can be reliably guaranteed. Furthermore, the atoms on the surface of single crystal particles have a particular arrangement, such as a (111) surface arrangement, that gives the material special mechanical, physical and chemical properties that can have beneficial effects.

[0245] Therefore, the present invention achieves the solid solution alloying of T element, M element, D element and La in the spherical or nearly spherical Fe-rich dispersed particle phase by precisely designing the alloy melt mainly composed of La and Fe, improving the corrosion resistance and oxidation resistance of the spherical or nearly spherical Fe-rich dispersed particle phase and reducing the impurity content. By removing the La-rich matrix phase, an ultrafine spherical iron alloy powder material with a particle size of several hundred nanometers to several micrometers is obtained, which has good application prospects in the fields of powder metallurgy, metal injection molding (MIM), 3D printing, magnetic materials, heat-resistant materials, high-temperature alloys, paints, electric heating materials, wave absorbing materials and the like.

[0246] Description: In the first to fourteenth aspects of the present invention, T comprises at least one of Cr and V, M comprises at least one of Al, Ni, Co, and Si, and D comprises at least one of Mo, W, and Ti. [Brief description of the drawings]

[0247] [Figure 1] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 1 of the present invention. [Diagram 2] 1 is a SEM morphological photograph of the iron alloy powder material produced in Example 1 of the present invention. [Diagram 3] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 2 of the present invention. [Figure 4] 1 is a high-magnification SEM morphological photograph of the backscattering of the matrix of the initial alloy solidification structure described in Example 2 of the present invention. [Diagram 5] 1 is a backscattered SEM morphological photograph of the initial alloy solidification structure described in Example 3 of the present invention. [Figure 6] 1 is a high-magnification SEM morphological photograph of the matrix of the initial alloy solidification structure described in Example 3 of the present invention. [Figure 7] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 4 of the present invention. [Figure 8] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 5 of the present invention. [Figure 9] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 6 of the present invention. [Figure 10] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 7 of the present invention. [Figure 11] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 8 of the present invention. [Figure 12] 1 is a SEM morphological photograph of an iron alloy powder material produced in Example 8 of the present invention. [Figure 13] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 10 of the present invention. [Figure 14] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 11 of the present invention. [Figure 15] 1 is a SEM morphological photograph of an iron alloy powder material produced in Example 11 of the present invention. [Figure 16] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 12 of the present invention. [Figure 17] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 13 of the present invention. [Figure 18] 1 is a SEM morphology photograph of the iron alloy powder material produced in Example 13 of the present invention. [Figure 19] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 14 of the present invention. [Figure 20] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 15 of the present invention. [Figure 21] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Example 16 of the present invention. [Figure 22] 1 is a SEM morphological photograph of the iron alloy powder material produced in Example 16 of the present invention. [Diagram 23] 1 is a backscattered SEM morphological photograph of the initial alloy solidification structure described in Comparative Example 1 of the present invention. [Figure 24] 1 is a SEM morphological photograph of an iron-rich dendrite described in Comparative Example 1 of the present invention. [Diagram 25] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Comparative Example 2 of the present invention. [Figure 26] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Comparative Example 3 of the present invention. [Figure 27] 1 is a backscattered SEM morphology photograph of the initial alloy solidification structure described in Comparative Example 4 of the present invention. [Figure 28] 1 is a high-magnification backscattered SEM morphological photograph of the initial alloy solidification structure described in Comparative Example 4 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0248] The present invention will be further described below with reference to specific examples. Note that the examples described below are intended to facilitate understanding of the present invention, but are not intended to limit the present invention in any way.

[0249] Example 1

[0250] Using commercially available La, Fe and Cr raw materials, the nominal composition La 50 Fe 41 Dissolves according to the atomic percentage of Cr9, La 50 Fe 41 An initial alloy melt containing Cr9 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 100 K / s to form an initial alloy plate with a thickness of about 5 mm. The solidification structure of the initial alloy plate was as shown in Figure 1. 79 Cr 20 The alloy contained a dispersed particle phase mainly composed of La1 and a matrix phase mainly composed of La, the volume percentage content of the matrix phase being 65% or more, Cr and La being solid-dissolved in the dispersed particle phase, the dispersed particle phase containing a spherical particle phase and a dendritic particle phase, the volume percentage content of the spherical particle phase being 50% or more, and the particle size range of the spherical particle phase being 15 nm to 60 μm.

[0251] The La matrix phase in the initial alloy plate was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 79 Cr 20 A dispersed iron alloy powder material with La1 as the main component was obtained. The dispersed iron alloy powder material contained spherical particles and dendritic particles, the volume percentage content of the spherical particles was more than 50%, and the particle size of the spherical particles was in the range of 15 nm to 60 μm, as shown in Figure 2. Some of the spherical or near-spherical particle phases contain certain dendritic features, such as small dendrite convex structures on the spherical particles, as shown in the inset of Figure 2. The manufactured iron alloy powder material can be used in the fields of general powder metallurgy and metal injection molding (MIM).

[0252] Example 2

[0253] Using commercially available La, Fe and Cr raw materials, the nominal composition La 50 Fe 41 Dissolves according to the atomic percentage of Cr9, La 50 Fe 41An initial alloy melt containing Cr9 as the main component was obtained. The homogeneous initial alloy melt was solidified by the free-strip method at a cooling rate of about 500 K / s to form an initial alloy strip with a thickness of about 200 μm. The solidification structure of the initial alloy strip was Fe 77 Cr 22 It contains a dispersed particle phase mainly composed of La1 and a matrix phase mainly composed of La, the volume percentage content of the matrix phase is more than 65%, most of the dispersed particle phase is spherical particles, and some of the spherical particle phase contains certain dendritic features, such as small dendrite convex structures on the spherical particles, as shown in the inset of Figure 3. The particle size range of the above spherical particle phase was 15 nm to 10 μm. When the matrix phase in Figure 3 is enlarged, some nano-spherical particles can also be seen inside, as shown in Figure 4.

[0254] The La matrix phase in the initial alloy strip was removed by reactive corrosion with a 0.5 mol / L dilute sulfuric acid aqueous solution, and the Fe 77 Cr 22 A dispersed iron alloy powder material containing La1 as the main component was obtained. The dispersed iron alloy powder material was almost entirely spherical particles, with a portion of the spherical particle phase containing specific dendritic features, and the particle size range of the spherical particles was 15 nm to 10 μm. The powder material produced can be used in the fields of general powder metallurgy and metal injection molding (MIM).

[0255] Example 3

[0256] Using commercially available La, Fe and V raw materials, the nominal composition La 67 Fe 30 Dissolved according to the atomic percentage of V3, La 67 Fe 30 An initial alloy melt containing V3 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 1000 K / s to form an initial alloy strip with a thickness of about 500 μm. The solidification structure of the initial alloy strip was Fe 88.5 V9La 1.5The matrix phase contained a dispersed particle phase mainly composed of La and a matrix phase mainly composed of La, the volume percentage content of the matrix phase was 70% or more, and most of the dispersed particle phase was spherical particles, with the particle size range of the spherical particle phase being 15 nm to 5 μm. When the matrix phase in Fig. 5 was enlarged, as shown in Fig. 6, some nanospherical particles were seen inside (anything other than the nanospherical particles was essentially the matrix phase), and a small number of the particle phases were dendritic particle phases.

[0257] The La matrix phase in the initial alloy strip was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 88.5 V9La 1.5 A dispersed iron alloy powder material containing the above-mentioned as a main component was obtained. The dispersed iron alloy powder material was mainly composed of spherical particles, with only a small amount of particle phase being dendritic particles, and the particle size range of the spherical particles was 15 nm to 5 μm.

[0258] Example 4

[0259] Using commercially available low-purity La, low-purity Fe, low-purity V, and low-purity Cr raw materials containing a large amount of O impurities, 67 Fe 30 Dissolves according to the atomic percentage of Cr3V3, La 65 Fe 30 An initial alloy melt containing Cr3V3O2 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was, as shown in Figure 7, Fe 82.3 V8Cr8La 1.5 O 0.2 and a matrix phase mainly composed of La and enriched in oxygen impurities, the volume percentage content of the matrix phase is more than 70%, the dispersed particle phase is mainly spherical and contains a small amount of dendrites, the particle size range of the spherical particle phase is 15 nm to 15 μm, and some of the spherical particle phase contains certain dendritic features.

[0260] The La-rich matrix phase in the initial alloy thick zone was removed by reactive corrosion with a 0.2 mol / L dilute nitric acid aqueous solution, and the Fe 82.3V8Cr8La 1.5 O 0.2 A dispersed iron alloy powder material was obtained, the shape of which was mainly spherical, with a small amount of dendritic shape, and part of the spherical particle phase contained certain dendritic features, and the particle size range of the spherical particles was 15 nm to 15 μm.

[0261] Example 5

[0262] Using commercially available La, Fe, Cr, and Mo raw materials, the nominal composition La 50 Fe 40 Cr 0.5 Mo 9.5 According to the atomic percentage of La 50 Fe 40 Cr 0.5 Mo 9.5 The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was as shown in Fig. 8. 78 Mo 20 The alloy comprises a dispersed particle phase mainly composed of Cr1La1 and a matrix phase mainly composed of La, the volume percentage content of the matrix phase is 70% or more, the dispersed particle phase is mainly spherical, the particle size range of the spherical dispersed particle phase is 15 nm to 15 μm, and some of the spherical particle phase contains certain dendritic features.

[0263] The La matrix phase in the initial alloy thick band was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 78 Mo 20 A dispersed iron alloy powder material mainly composed of Cr1La1 was obtained. The dispersed iron alloy powder material was mainly in the form of spherical particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 15 μm.

[0264] Example 6

[0265] Using commercially available La, Fe, Cr, and Si raw materials, the nominal composition La 34 Fe 40 Cr 2.5S 23.5 According to the atomic percentage of La 34 Fe 40 Cr 2.5 S 23.5 The homogeneous initial alloy melt was solidified at a cooling rate of about 100 K / s to form an initial alloy band with a thickness of about 5 mm. The solidification structure of the initial alloy band was as shown in Fig. 9. 85.2 Cr8Si6La 0.8 The black dispersed particle phase is mainly composed of La 64 S 36 The white matrix phase is mainly composed of La 34 S 33 Fe 33 and a gray matrix phase mainly composed of these two matrix phases, the volume percentage content of which was 70% or more, the shape of the dispersed particle phase was mainly nearly spherical, and the particle size range of the nearly spherical particle phase was 50 nm to 5 μm.

[0266] La in the initial alloy thick zone 64 S 36 Matrix phase and La 34 S 33 Fe 33 The matrix phase was removed by reactive corrosion with a mixture of 0.5 mol / L dilute hydrochloric acid and 1 mol / L hydrofluoric acid, and the Fe 85.2 Cr8Si6La 0.8 A dispersed iron alloy powder material containing the above as a main component was obtained. The shape of the dispersed iron alloy powder material was mainly close to spherical, and the particle size range of the above particles close to spherical was 50 nm to 5 μm. The manufactured powder material can be used in the field of magnetic materials such as dust cores.

[0267] Example 7

[0268] Using commercially available La, Fe, Cr, and Si raw materials, the nominal composition La 34 Fe 40 Cr 2.5 S 23.5 According to the atomic percentage of La 34 Fe 40 Cr 2.5 S 23.5The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 5 The alloy was solidified at a cooling rate of 100 K / s to form an initial alloy strip with a thickness of about 100 μm. The solidification structure of the initial alloy strip was Fe 82.5 Cr8Si8La 1.5 The black dispersed particle phase is mainly composed of La 60 S 20 Fe 20 The matrix phase had an average composition mainly composed of the above, the volume percentage content of the matrix phase was 70% or more, the dispersed particle phase was mainly fine and spherical, and the particle size range of the spherical particle phase was 15 nm to 2 μm.

[0269] La in the initial alloy strip 60 S 20 Fe 20 The matrix phase, which has an average composition mainly composed of Fe, was removed by reactive corrosion with a mixture of 0.5 mol / L dilute hydrochloric acid and 1 mol / L hydrofluoric acid, and Fe 82.5 Cr8Si8La 1.5 A dispersed iron alloy powder material containing Si and composed mainly of was obtained. The shape of the dispersed iron alloy powder material was mainly close to spherical, and the particle size range of the close to spherical particles was 15 nm to 2 μm. The produced powder material can be used in the field of magnetic materials such as dust cores.

[0270] Example 8

[0271] Using commercially available La, Fe, Cr, and Si raw materials, the nominal composition La 50 Fe 40 Dissolves according to the atomic percentage of Cr5Si5, La 50 Fe 40 An initial alloy melt containing Cr5Si5 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was, as shown in Figure 11, Fe 86 Cr 12 The dispersed particle phase is mainly composed of Si1La1, and the La 92and a matrix phase mainly composed of Si8, the volume percentage content of the matrix phase being 70% or more, the dispersed particle phase being mainly spherical and also containing a small amount of dendritic particles, and a part of the spherical particle phase having a certain dendritic feature, the particle size range of the spherical particle phase being 15 nm to 40 μm.

[0272] The LaSi matrix phase in the initial alloy strip was removed by reactive corrosion with a mixture of 0.5 mol / L dilute hydrochloric acid, 0.1 mol / L dilute nitric acid, and 0.5 mol / L hydrofluoric acid (hydrofluoric acid can remove Si), and Fe 86 Cr 12 A dispersed iron alloy powder material mainly composed of Si1La1 was obtained. As shown in Fig. 12, the dispersed iron alloy powder material was mainly spherical, and also contained a small amount of dendritic particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particle phase was 15 nm to 40 μm.

[0273] Example 9

[0274] Using commercially available La, Fe, Cr, and Si raw materials, the nominal composition La 50 Fe 41 Dissolves according to the atomic percentage of Cr4Si5, La 50 Fe 41 An initial alloy melt containing Cr4Si5 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 1000 K / s to form an initial alloy strip having a thickness of about 500 μm. The solidification structure of the initial alloy strip was Fe 90.5 Cr8Si 0.5 The dispersed particle phase is mainly composed of La1, and the La 94 and a matrix phase mainly composed of Si6, the volume percentage content of the matrix phase being 70% or more, the dispersed particle phase being mainly spherical and also containing a small amount of dendritic particles, and a part of the spherical particle phase having a certain dendritic character, the particle size range of the spherical particle phase being 15 nm to 10 μm.

[0275] La in the LaSi matrix phase of the initial alloy strip was removed by dealloying with 0.5 mol / L dilute hydrochloric acid, while most of the Si was retained (Si generally does not react with dilute hydrochloric acid), and Fe 90.5 Cr8Si 0.5 A composite powder of iron alloy powder mainly composed of La1 and nanoporous Si was obtained. The nanoporous Si has a fragmented porous structure, the iron alloy powder material is mainly spherical particles, and also contains a small amount of dendritic particles, and part of the spherical particle phase has a certain dendritic feature, and the particle size range of the spherical particle phase is 15 nm to 10 μm.

[0276] The spherical iron alloy powder and nanoporous Si composite powder were press molded, and then vacuum solid silicon infiltration was performed at 1000°C for 4 hours to disperse the powder and obtain approximately Fe 82 Cr7Si 10 An iron-chromium-silicon powder with a high Si content and a composition of La1 was obtained.

[0277] The produced iron-chromium-silicon powder with a high Si content is sieved and selected to have a particle size of 3 μm to 10 μm, and can be used in the field of soft magnetic materials such as powder magnetic cores.

[0278] Example 10

[0279] Using commercially available La, Fe, Cr, and Al raw materials, 45 Fe 27.5 Cr 7.5 Al 20 According to the atomic percentage of La 45 Fe 27.5 Cr 7.5 Al 20 The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy thick band with a thickness of about 3 mm. The solidification structure of the initial alloy thick band was, as shown in Fig. 13, Fe 72 Cr 20 A l7 The dispersed particle phase is mainly composed of La1, and the La 75 Al 25and a matrix phase mainly composed of, the volume percentage content of the matrix phase being 70% or more; the dispersed particle phase being mainly spherical and also containing a small amount of dendritic particles, and a part of the spherical particle phase having a certain dendritic feature, the particle size range of the spherical particle phase being 15 nm to 10 μm.

[0280] La in the initial alloy thick band 75 Al 25 The matrix phase was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 72 Cr 20 A dispersed iron alloy powder material mainly composed of Al7La1 was obtained. The dispersed iron alloy powder material was mainly spherical particles, and also contained a small amount of dendritic particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 10 μm. The powder material produced can be used in the fields of electric heating alloys, heat-resistant alloys, and heat-resistant paints.

[0281] Example 11

[0282] Using commercially available La, Fe, Cr, and Al raw materials, 45 Fe 27.5 Cr 7.5 Al 20 According to the atomic percentage of La 45 Fe 27.5 Cr 7.5 Al 20 The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 4 The alloy was solidified at a cooling rate of 100 K / s to form an initial alloy ribbon with a thickness of about 150 μm. The solidification structure of the initial alloy ribbon was as shown in FIG. 14. 71 Cr 21 A l7 The dispersed particle phase is mainly composed of La1, and the La 75 Al 25 and a matrix phase mainly composed of, the volume percentage content of the matrix phase being 70% or more, the dispersed particle phase being almost entirely spherical, and a portion of the spherical particle phase having a certain dendritic characteristic, the particle size range of the spherical particle phase being 5 nm to 5 μm.

[0283] La in the initial alloy thick band 75 Al 25 The matrix phase was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 71 Cr 21 A dispersed iron alloy powder material mainly composed of Al7La1 was obtained. The dispersed iron alloy powder material was almost entirely spherical, as shown in FIG. 15, and part of the spherical particle phase contained certain dendritic features. As shown in the inset of FIG. 15, the particle size range of the spherical particles was 5 nm to 5 μm. The powder material produced can be used in the fields of electric heating alloys, heat-resistant alloys, and heat-resistant paints.

[0284] Example 12

[0285] Using commercially available La, Fe, Cr, Al, and Mo raw materials, the nominal composition La 38 Fe 25 Cr 10 Al 25 Dissolves according to the atomic percentage of Mo2, La 38 Fe 25 Cr 10 Al 25 An initial alloy melt containing Mo2 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 500 K / s to form an initial alloy band with a thickness of about 1 mm. The solidification structure of the initial alloy band was, as shown in Figure 16, Fe 60 Cr 25 The dispersed particle phase is mainly composed of Al8Mo6La1, and the La 50 Al 50 (gray slate and fibrous facies) and La 75 Al 25 The matrix phase contained a white phase as a main component, and the volume percentage content of the matrix phase was 70% or more. The dispersed particle phase was mainly spherical and also contained a small amount of dendritic particles, and a portion of the spherical particle phase contained certain dendritic characteristics. The particle size range of the spherical particle phase was 15 nm to 40 μm.

[0286] La in the initial alloy thick band 50 Al 50 and La 75 Al 25The matrix phase was removed by reactive corrosion with a 1 mol / L dilute hydrochloric acid solution, and the Fe 60 Cr 25 A dispersed iron alloy powder material with Al8Mo6La1 as the main component was obtained. The dispersed iron alloy powder material was mainly spherical particles, and also contained a small amount of dendritic particles, and part of the spherical particle phase contained certain dendritic features, and the particle size range of the spherical particles was 15nm-40μm. The produced powder material can be used in the fields of electric heating alloys, heat-resistant alloys, and heat-resistant paints. Due to the presence of Mo, the powder material has higher heat resistance and corrosion resistance.

[0287] Example 13

[0288] Using commercially available La, Fe, Cr, and Co raw materials, the nominal composition La 27.5 Fe 37.5 Cr 10 Co 25 According to the atomic percentage of La 27.5 Fe 37.5 Cr 10 Co 25 The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was, as shown in Figure 17, Fe 63 Cr 19 Co 17 The dispersed particle phase is mainly composed of La1, and the La 60 Co 40 and a matrix phase mainly composed of, the volume percentage content of the matrix phase being 50% or more, the dispersed particle phase being almost entirely spherical with only a small number of dendritic shapes, and a portion of the spherical particle phase having certain dendritic characteristics, the particle size range of the spherical particle phase being 15 nm to 6 μm.

[0289] La in the initial alloy thick band 60 Co 40 The matrix phase was removed by reactive corrosion with a 1 mol / L dilute hydrochloric acid solution, and the Fe 63 Cr 19 Co 17A dispersed iron alloy powder material containing La1 as the main component was obtained. The dispersed iron alloy powder material was mainly spherical particles, and also contained a small amount of dendritic particles, as shown in Figure 18, and part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 6 μm. The produced powder material can be used in the field of magnetic materials.

[0290] Example 14

[0291] Using commercially available La, Fe, Cr, and Ni raw materials, the nominal composition La 27.5 Fe 37.5 Cr 10 Ni 25 According to the atomic percentage of La 27.5 Fe 37.5 Cr 10 Ni 25 The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was, as shown in Figure 19, Fe 70 Cr 20 The dispersed particle phase is mainly composed of Ni9La1, and the La 50 Ni 50 and La 75 Ni 25 and a matrix phase mainly composed of, the total volume percentage content of the matrix phase being 50% or more, the dispersed particle phase being mainly spherical particles with a small amount of dendritic particles, and a part of the spherical particle phase having a certain dendritic feature, the particle size range of the spherical particle phase being 15 nm to 50 μm.

[0292] La in the initial alloy thick band 50 Ni 50 and La 75 Ni 25 The matrix phase was removed by reactive corrosion with a 1 mol / L dilute hydrochloric acid solution, and the Fe 70 Cr 20 A dispersed iron alloy powder material mainly composed of Ni9La1 was obtained. The dispersed iron alloy powder material was mainly spherical particles, and also contained a small amount of dendritic particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 50 μm.

[0293] Example 15

[0294] Using commercially available La, Fe, Cr, Ni, Mo, and Ti raw materials, the nominal composition La 35 Fe 36 Cr 10 Ni 15 Dissolves according to the atomic percentage of Mo1Ti2, La 35 Fe 36 Cr 10 Ni 15 An initial alloy melt containing Mo1Ti2 as the main component was obtained. The homogeneous initial alloy melt was solidified at a cooling rate of about 50 K / s to form a button ingot with a thickness of 6 mm and a diameter of 12 mm. The solidification structure of the initial alloy button ingot was Fe, as shown in Figure 20. 70 Cr 20 The dispersed particle phase is mainly composed of Ni3Mo2Ti4La1, and the La 81 Ni 19 The matrix phase contained a matrix phase mainly composed of La phase and La3Ni phase, the total volume percentage content of the matrix phase was 70% or more, the dispersed particle phase was almost entirely spherical with only a small number of dendritic shapes, and a portion of the spherical particle phase contained certain dendritic characteristics, and the particle size range of the spherical particle phase was 15 nm to 50 μm.

[0295] La in the initial alloy button ingot 81 Ni 19 The matrix phase was removed by reactive corrosion with a 1 mol / L dilute hydrochloric acid solution, while the corrosion-resistant dispersed particle phase was retained. 70 Cr 20 A dispersed iron alloy powder material mainly composed of Ni3Mo2Ti4La1 was obtained. The dispersed iron alloy powder material was mainly spherical particles, and also contained a small amount of dendritic particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 50 μm.

[0296] Example 16

[0297] Using commercially available La, Fe, Cr, and Ni raw materials, the nominal composition La 27.5 Fe37.5 Cr 10 Ni 25 According to the atomic percentage of La 27.5 Fe 37.5 Cr 10 Ni 25 The homogeneous initial alloy melt was solidified at a cooling rate of about 5000 K / s to form an initial alloy strip with a thickness of about 200 μm. The solidification structure of the initial alloy strip was, as shown in FIG. 21, Fe 70 Cr 20 The dispersed particle phase is mainly composed of Ni9La1, and the La 60 Ni 40 and a matrix phase mainly composed of, the total volume percentage content of the matrix phase being 50% or more, the dispersed particle phase being almost entirely spherical with only a small number of dendritic shapes, and a portion of the spherical particle phase having certain dendritic characteristics, the particle size range of the spherical particle phase being 15 nm to 6 μm.

[0298] The La in the matrix phase in the initial alloy strip was removed by dealloying with 0.2 mol / L dilute hydrochloric acid, while part of the nanoporous Ni was retained and Fe 70 Cr 20 A composite powder of dispersed iron alloy powder mainly composed of Ni9La1 and nanoporous Ni was obtained. As shown in Figure 22, the outer flocs of the spherical particles are nanoporous Ni, the iron alloy powder material is mainly spherical particles, and also contains a small amount of dendritic particles, and part of the spherical particle phase contains a certain dendritic feature, and the particle size range of the spherical particle phase is 15nm-6μm.

[0299] Fe 70 Cr 20 The spherical iron alloy powder material, mainly composed of Ni9La1, and the composite powder of nanoporous Ni were pressed into a billet at 100 MPa, and then heat-treated at 1300°C for 4 hours in a protective atmosphere to remove approximately Fe. 52 Cr 15 Ni 33 The iron-chromium-nickel high temperature alloy product with high Ni content and the detected composition of La1 was obtained.

[0300] Example 17

[0301] Using commercially available La, Fe, and Cr raw materials, the nominal composition La 45 Fe 40 Cr 15 According to the atomic percentage of La 45 Fe 40 Cr 15 The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 6 K / s-10 7 The alloy strip was solidified at a cooling rate of 1000 K / s to form an initial alloy strip with a thickness of about 20 μm. The solidification structure of the initial alloy strip included an Fe-rich dispersed nanoparticle phase (the particles were too small to be directly detected) and a matrix phase mainly composed of La, the volume percentage content of the matrix phase was 60% or more, the dispersed nanoparticle phase was almost entirely spherical in shape, and some of the spherical nanoparticle phase contained certain dendritic features, and the particle size range of the spherical nanoparticle phase was 5 nm to 200 nm.

[0302] The La matrix phase in the initial alloy strip was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 71 Cr 27 A dispersed iron alloy powder material containing La2 as the main component was obtained (Fe 71 Cr 27 The La2 nano-iron alloy powder particles are not easily dissolved by acid reaction. The dispersed iron alloy powder material is almost entirely spherical particles, and a part of the spherical particle phase contains certain dendritic features, and the particle size range of the nano-iron alloy powder material is 5 nm to 200 nm.

[0303] Example 18

[0304] Using commercially available La, Fe, and Cr raw materials, the nominal composition La 50 Fe 46 Dissolves according to the atomic percentage of Cr4, La 50 Fe 46 The initial alloy melt, which was mainly composed of Cr4, was obtained. The homogeneous initial alloy melt was 4The alloy was solidified at a cooling rate of 100 K / s to form an initial alloy strip with a thickness of about 150 μm. The solidification structure of the initial alloy strip was Fe 91 The alloy contained a dispersed particle phase mainly composed of Cr8La1 and a matrix phase mainly composed of La, in which Cr and La were dissolved in the dispersed particle phase, the iron-rich dispersed particle phase mainly contained spherical particles and also contained a small amount of dendritic particle phase, and some of the spherical particle phase contained certain dendritic characteristics, and the particle size range of the iron-rich spherical particle phase was 15 nm to 10 μm.

[0305] The La matrix phase in the initial alloy strip was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 91 A dispersed iron alloy powder material mainly composed of Cr8La1 was obtained, which contained spherical particles and dendritic particles, mainly spherical particles, and a part of the spherical particle phase contained a certain dendritic feature, and the particle size range of the spherical particles was 15 nm to 10 μm.

[0306] The iron alloy powder material obtained above is infiltrated with gaseous silicon in a mixture of silicon chloride (SiCl4, Si2Cl6, or a mixture of SiCl4 and Si2Cl6) and hydrogen at a processing temperature of 400°C to 1000°C, resulting in a composition of approximately Fe 81.5 Cr7Si 10.5 A spherical iron alloy powder material was obtained with a Si content of La1. The shape of the spherical iron alloy powder material was almost the same as before the silicon infiltration treatment, and it contained spherical particles and dendritic particles, mainly consisting of spherical particles, and some of the spherical particles contained specific dendritic features, and the particle size of the spherical particles was 15 nm to 10 μm.

[0307] After sieving, 1μm-10μm Fe 81.5 Cr7Si 10.5 La1 powder was selected for the insulating coating to produce powder cores.

[0308] Example 19

[0309] Using commercially available La, Fe, and Cr raw materials, the nominal composition La 35 Fe 50 Cr 15According to the atomic percentage of La 35 Fe 50 Cr 15 The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 3 K / s-10 6 The initial alloy powder was solidified by atomization at a cooling rate of 100 K / s to form an initial alloy powder with a particle size of 5 μm to 300 μm. The solidification structure of the initial alloy powder was Fe 75.5 Cr 23 La 1.5 The matrix phase had a volume percentage content of 50% or more, the dispersed particle phase was almost entirely spherical particles, and a portion of the spherical particle phase had a certain dendritic characteristic, and the particle size range of the spherical particle phase was 5 nm to 10 μm.

[0310] The La matrix phase in the initial alloy powder was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 75.5 Cr 23 La 1.5 A dispersed fine iron alloy powder material was obtained, the main component of which was . The dispersed fine iron alloy powder material was almost entirely spherical particles, with a portion of the spherical particle phase containing certain dendritic features, and the particle size range of the spherical particles was 5 nm to 10 μm. The produced powder material can be used in the fields of general powder metallurgy and metal injection molding (MIM).

[0311] Example 20

[0312] Using commercially available La, Fe, Mo, and Cr raw materials, the nominal composition La 50 Fe 49 Cr 0.5 Mo 0.5 According to the atomic percentage of La 50 Fe 49 Cr 0.5 Mo 0.5 The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 7 K / s-10 8The alloy strip was solidified at a cooling rate of 100 K / s to form an initial alloy strip having a thickness of about 15-20 μm. The solidification structure of the initial alloy strip included an Fe-rich dispersed nanoparticle phase and a La-based matrix phase, the volume percentage content of the matrix phase was 65% or more, the dispersed nanoparticle phase was almost entirely spherical nanoparticles, and a part of the spherical particle phase included certain dendritic features, and the particle size range of the spherical particle phase was 5 nm to 100 nm.

[0313] The La matrix phase in the initial alloy strip was removed by reactive corrosion with 0.25 mol / L dilute hydrochloric acid solution, and the Fe 97 A nano-iron alloy powder material consisting mainly of Cr1Mo1La1 was obtained (due to the presence of Cr and Mo, nano-Fe 97 The Cr1Mo1La1 iron alloy powder particles are difficult to dissolve in 0.25mol / L dilute hydrochloric acid. The nano-iron alloy powder material is almost entirely spherical particles, and part of the spherical particle phase contains certain dendritic features. 97 The particle size range of Cr1Mo1La1Fe alloy powder particles was 5nm-100nm.

[0314] The obtained nano-Fe 97 The magnetic fluid was prepared using Cr1Mo1La1 iron alloy powder particles as magnetic solid particles, sodium dodecyl sulfate (SDS) and oleic acid as surfactants, and ethanol as carrier fluid.

[0315] Example 21

[0316] Using commercially available La, Fe, and Cr raw materials, the nominal composition La 50 Fe 47 Dissolves according to the atomic percentage of Cr3, La 50 Fe 47 The initial alloy melt, which was mainly composed of Cr3, was obtained. The homogeneous initial alloy melt was 6 K / s-10 8The alloy strip was solidified at a cooling rate of 100 K / s to form an initial alloy strip having a thickness of about 15-20 μm. The solidification structure of the initial alloy strip included an Fe-rich dispersed nanoparticle phase and a La-based matrix phase, the volume percentage content of the matrix phase was 65% or more, the dispersed nanoparticle phase was almost entirely spherical nanoparticles, and a part of the spherical particle phase included certain dendritic features, and the particle size range of the spherical particle phase was 5 nm to 50 nm.

[0317] The La matrix phase in the initial alloy strip was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 93 A nano-iron alloy powder material consisting mainly of Cr6La1 was obtained (due to the presence of Cr, nano-Fe 93 The Cr6La1 iron alloy powder particles are difficult to dissolve in 0.5 mol / L dilute hydrochloric acid. The nano-iron alloy powder material is almost entirely spherical particles, and part of the spherical particle phase contains certain dendritic features. 93 The particle size range of Cr6La1 iron alloy powder particles was 5nm-50nm.

[0318] The obtained nano-Fe 93 The magnetic fluid was prepared using Cr6La1 iron alloy powder particles as the magnetic solid particles and mercury as the carrier fluid.

[0319] Comparative Example 1

[0320] Using commercially available La and Fe raw materials, the nominal composition La 50 Fe 50 According to the atomic percentage of La 50 Fe 50 The homogeneous initial alloy melt was solidified at a cooling rate of about 250 K / s to form an initial alloy band with a thickness of about 3 mm. The solidification structure of the initial alloy band was as shown in Fig. 23, 99It contained a dispersed particle phase mainly composed of La1 and a matrix phase mainly composed of La, the volume percentage content of the matrix phase was 70% or more, and the dispersed particle phase was almost entirely dendritic. The regularly arranged, seemingly spherical parts in Figure 23 were actually the cross-sectional form of dendritic branches, and each row of cross-sectional branches actually belonged to a large dendrite.

[0321] The La matrix phase in the initial alloy thick band was removed by reactive corrosion with a 0.5 mol / L dilute hydrochloric acid solution, and the Fe 99 A dispersed iron alloy dendritic powder material containing La1 as the main component was obtained. As shown in FIG. 24, the dispersed iron alloy dendritic powder material was mainly in the shape of dendrites, and no spherical particles were observed. It was also clear that the large dendrites had rows of secondary dendrites, and the cross sections of these secondary dendrites corresponded to a regular arrangement of the cross-sectional morphology of the "ball" (actually a rod-like cross section) shape shown in FIG. 23. Therefore, it was confirmed that La 50 Fe 50 The alloy can only obtain large iron-rich dendritic grains with sufficient growth by slow cooling, but not iron-rich spheroidal grains.

[0322] Comparative Example 2

[0323] Using commercially available La and Fe raw materials, the nominal composition La 50 Fe 50 According to the atomic percentage of La 50 Fe 50 The initial alloy melt was obtained with a homogeneous initial alloy melt of about 10 5 The alloy was solidified at a cooling rate of 100 K / s to form an initial alloy strip with a thickness of about 100 μm. The solidification structure of the initial alloy strip was Fe 99 The dispersed particle phase is composed mainly of La1 and the matrix phase is composed mainly of La. The dispersed particle phase is almost entirely dendritic. The adjacent iron-rich black phases, which appear as short rods in Figure 25, actually belong to one or more dendrites, and the size of these dendrites is about 1 to 2 μm. The nanoscale secondary structure of the dendrites and the Fe 99Because La1 is not resistant to acid corrosion, when acid corrosion is adopted, the nanoscale iron-rich dendrites are also reactively corroded, making it difficult to obtain pristine iron-rich particles. Therefore, even if the cooling rate is very fast, if the initial alloy melt does not contain T and D elements, on the one hand, it is difficult to obtain spherical iron-rich particle phase, and on the other hand, the corrosion resistance of iron-rich particles, which are easily separated by acid reaction, cannot be improved.

[0324] Comparative Example 3

[0325] Using commercially available La, Fe, and Hf raw materials, the nominal composition La 50 Fe 40 Hf 10 According to the atomic percentage of La 50 Fe 40 Hf 10 The homogeneous initial alloy melt was solidified at a cooling rate of about 500 K / s to form an initial alloy band with a thickness of about 1 mm. The solidification structure of the initial alloy band was, as shown in Figure 26, approximately Fe 99 Black dispersed dendritic phase composed mainly of La1, approximately Fe 64 Hf 35 The alloy consisted of a white dispersed dendritic phase mainly composed of La1, and a matrix phase mainly composed of La. Therefore, Hf in the initial alloy melt cannot dissolve in the Fe-rich phase during the solidification of the melt, and can only precipitate as Fe2Hf intermetallic compounds. On the other hand, the Fe-rich phase mainly consists of Fe 99 The La1 precipitates as a dispersed dendritic phase, and the spheroidal grain phase is not obtained with both dendritic phases. Therefore, when Hf is added to La-Fe alloys, the Fe-rich spheroidal grain phase is not obtained.

[0326] Comparative Example 4

[0327] Using commercially available La, Fe, and Ta raw materials, the nominal composition La 50 Fe 40 Ta 10 According to the atomic percentage of La 50 Fe 40 Ta 10The homogeneous initial alloy melt was solidified at a cooling rate of about 500 K / s to form an initial alloy band with a thickness of about 1 mm. The solidification structure of the initial alloy band was, as shown in Figure 27, approximately Fe 99 Black dispersed dendritic phase composed mainly of La1, approximately Fe 69 Ta 30 It consisted of a white aggregated dendritic phase mainly composed of La1 (which is an Fe7Ta3 intermetallic compound, as shown by the arrow in Figure 28), and a matrix phase mainly composed of La. Therefore, Ta in the initial alloy melt cannot dissolve in the Fe-rich phase during the solidification of the melt, and can only precipitate as the Fe7Ta3 intermetallic compound. On the other hand, the Fe-rich phase mainly consists of Fe 99 The La1 precipitates as a dispersed dendritic phase, and the spheroidal grain phase is not obtained with both dendritic phases. Therefore, when Ta is added to the La-Fe alloy, the Fe-rich spheroidal grain phase is not obtained.

[0328] The technical features of the above-described embodiments may be combined in any manner. For the sake of brevity, all possible combinations of the technical features in the above embodiments have not been described, but as long as there is no contradiction in the combination of these technical features, they should be considered as within the scope described in this specification.

[0329] The above-described examples merely show some embodiments of the present invention, and the description is relatively specific and detailed, but this should not be understood as limiting the scope of protection of the invention. However, those skilled in the art can make some modifications and improvements without departing from the concept of the present invention, and all of these belong to the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the appended claims.

Claims

1. A method for producing a spherical iron alloy powder material, comprising the steps of: Step 1: Selecting an initial alloy raw material, melting the initial alloy raw material according to an initial alloy composition ratio to obtain a homogeneous initial alloy melt, the main composition of the initial alloy melt being La x Fe y T z M a D b Step 1, in which T includes at least one of Cr and V, M includes at least one of Al, Ni, Co and Si, D includes at least one of Mo, W and Ti, and x, y, z, a and b are the atomic percentage contents of the corresponding elements, respectively, and 18%≦x≦95.8%, 4%≦y≦81.8%, 0.1%≦z≦35%, 0≦a≦40%, 0≦b≦15%; Step 2 is to solidify the initial alloy melt into an initial alloy solid by a rapid solidification technique, the solidification structure of the initial alloy solid includes a matrix phase and a dispersed particle phase, the matrix phase has a melting point lower than that of the dispersed particle phase, the dispersed particle phase is contained in the matrix phase, the volume percentage content of the matrix phase in the solidification structure is 40% or more, and the average composition of the matrix phase is mainly La x1 M a1 The composition of the dispersed particle phase is mainly Fe y2 T z2 M a2 D b2 La x2 Step 2, in which x1, a1, x2, y2, z2, a2, and b2 are the atomic percentage contents of the corresponding constituent elements, and 45%≦x1≦100%, 0%≦a1≦55%, 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, and 0<x2≦5%, the dispersed particle phase includes a substantial amount of spherical or nearly spherical dispersed particle phase, a portion of the spherical or nearly spherical dispersed particle phase includes specific dendritic features, and the particle size of the dispersed particle phase is 5 nm to 50 μm; The matrix phase is removed from the initial alloy solid, and mainly the dispersed particle phase is retained, and Fe y2 T z2 M a2 D b2 La x2 Step 3 of obtaining an iron alloy powder material mainly composed of 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, 0<x2≦5%, the iron alloy powder particles contain a substantial amount of spherical or near-spherical particles, a portion of the spherical or near-spherical iron alloy powder particles contain specific dendritic features, and the iron alloy powder particles have a particle size of 5 nm to 50 μm; A method for producing a spherical iron alloy powder material, comprising:

2. 2. The method for producing a spherical iron alloy powder material according to claim 1, wherein the dispersed particle phase has a shape that is mainly spherical or nearly spherical.

3. The method for producing spherical iron alloy powder material according to claim 1, characterized in that the composition of the initial alloy melt in step 1 further includes non-metallic impurity elements, the non-metallic impurity elements including at least one of O, N, H, P, S, and Cl, and the atomic percentage content of the non-metallic impurity elements in the initial alloy melt is greater than 0 and less than 10%; during the formation of the Fe-rich dispersed particle phase in step 2, the non-metallic impurity elements are enriched in the La-rich matrix phase, thereby refining the Fe-rich dispersed particle phase, i.e., the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is lower than that in the initial alloy melt, and the atomic percentage content of the non-metallic impurity elements in the Fe-rich dispersed particle phase is less than 1.5%; and the content of the non-metallic impurity elements in the spherical or nearly spherical iron alloy powder particles in step 3 is also lower than that in the initial alloy melt.

4. An alloy powder produced by the method for producing a spherical iron alloy powder material according to any one of claims 1 to 3, Some features of the spherical iron alloy powder material include: The main composition of the spherical iron alloy powder material is Fe. y2 T z2 M a2 D b2 La x2 wherein 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, and 0<x2≦5%, the iron alloy powder particles are mainly spherical or nearly spherical in shape, and some of the spherical or nearly spherical iron alloy powder particles include certain dendritic characteristics, the particle size range of the iron alloy powder particles is 5 nm to 50 μm, T includes at least one of Cr and V, M includes at least one of Al, Ni, Co, and Si, D includes at least one of Mo, W, and Ti, and x1, a1, x2, y2, z2, a2, and b2 respectively represent the atomic percentage content of the corresponding constituent elements.

5. A method for producing a spherical iron-chromium-silicon powder material with a high Si content, comprising the steps of: subjecting a spherical iron alloy powder material whose main component element is Fe-Cr, produced by steps 1 to 3 as described in claim 1, or a spherical iron alloy powder material whose main component element is Fe-Cr-Si and has a low Si content, to a Si infiltration treatment to obtain a spherical powder material whose main component element is Fe-Cr-Si and has a high Si content.

6. According to the steps 1 and 2 of claim 1, the initial alloy solid according to step 2 of claim 1 is produced, wherein T comprises Cr, M comprises Si, and 0<a≦40%, and the average composition of the matrix phase is mainly La. x1 S a1 The composition of the dispersed particle phase is mainly Fe with a low Si content. y2 Cr z2 S a2 D b2 La x2 and the La x1 S a1 The Si in the matrix phase is bonded to La by an intermetallic compound, and 0<a2≦8%. x1 S a1 La in the matrix phase is the original La x1 S a1 The Si in the matrix phase is removed by a dealloying reaction using a dilute acid solution while retaining the Si, and the nanoporous Si and the Fe with a low Si content are obtained. y2 Cr z2 S a2 D b2 La x2 A composite powder of nanoporous Si particles is obtained, and the nanoporous Si is a Fe with a low Si content. y2 Cr z2 S a2 D b2 La x2 Used as a Si source for infiltrating Si into particles, with a composition mainly of Fe y3 Cr z3 S a3 D b3 La x3 The method for producing spherical iron-chromium-silicon powder material with a high Si content as described above, characterized in that x3, y3, z3, a3, and b3 respectively represent the atomic percentage contents of the corresponding constituent elements, and are 0<y3<y2, 0<z3<z2, 0<a2<a3, 0≦b3≦b2, and 0<x3<x2.

7. A spherical iron-chromium-silicon powder material with a high Si content, which is produced by the method for producing a spherical iron-chromium-silicon powder material with a high Si content as set forth in claim 5.

8. The method of claim 6 provides nanoporous Si and Fe with low Si content. y2 Cr z2 S a2 D b2 La x2 The composite powder of nanoporous Si and spherical Fe—Cr—Si particles is obtained by producing a composite powder of nanoporous Si and spherical Fe—Cr—Si particles.

9. A method for producing an iron-chromium-nickel powder metallurgy product with a high nickel content, comprising the steps of producing an initial alloy solid according to step 2 of claim 1 according to steps 1 and 2 of claim 1, wherein T comprises Cr, M comprises Ni, and 0<a≦40%, and the average composition of the matrix phase is mainly La. x1 Ni a1 The composition of the dispersed particle phase is mainly Fe with a low Ni content. y2 Cr z2 Ni a2 D b2 La x2 and the La x1 Ni a1 Step 1, in which Ni in the matrix phase is bonded to La by an intermetallic compound, and 0<a2≦12%; The initial alloy solid La x1 Ni a1 La in the matrix phase is the original La x1 Ni a1 While most of the Ni in the matrix phase is not removed by the reaction, it is removed by a dealloying reaction with a dilute acid solution, resulting in nanoporous Ni and Fe with a low Ni content. y2 Cr z2 Ni a2 D b2 La x2 Step 2 of obtaining a composite powder of particles; Nanoporous Ni and Fe with low Ni content y2 Cr z2 Ni a2 D b2 La x2 The composite powder of the particles is press molded, heat treated and sintered to form a composite material having a main component composition of Fe. y3 Cr z3 Ni a3 D b3 La x3 Step 3: obtaining a FeCrNi powder metallurgy product having a high Ni content, wherein x3, y3, z3, a3 and b3 respectively represent the atomic percentage contents of the corresponding constituent elements, and 0<y3<y2, 0<z3<z2, 0<a2<a3, 0≦b3≦b2, and 0<x3<x2; 1. A method for producing an iron-chromium-nickel powder metallurgy product with a high nickel content, comprising:

10. 10. An iron-chromium-nickel powder metallurgy product with a high nickel content, which is produced by the method for producing an iron-chromium-nickel powder metallurgy product with a high nickel content as claimed in claim 9.

11. A composite powder of nanoporous Ni and iron-chromium-nickel particles with low Ni content, characterized in that it is produced by steps 1 and 2 of the method according to claim 9.

12. Use of the spherical alloy iron powder material according to claim 4 in any one of the fields of general powder metallurgy, metal injection molding (MIM), 3D printing, magnetic materials, heat-resistant materials, high-temperature alloys, paints, and wave absorbing materials.

13. The use of the spherical ferroalloy powder material according to claim 4 in the field of electric heating materials, characterized in that the spherical ferroalloy powder material is mainly composed of Fe-Cr-Al.

14. Use of the spherical iron-chromium-silicon powder material with a high Si content according to claim 7 in a magnetic material.

15. Use of the high nickel content iron-chromium-nickel powder metallurgy product according to claim 10 in high temperature alloys.

16. Selecting initial alloy raw materials, melting the initial alloy raw materials according to the initial alloy composition ratio, and obtaining a homogeneous initial alloy melt, the main component of the initial alloy melt being La. x Fe y T z M a D b Step 1, in which T includes at least one of Cr and V, M includes at least one of Al, Ni, Co, and Si, D includes at least one of Mo, W, and Ti, and x, y, z, a, and b each represent the atomic percentage content of the corresponding constituent element, and 18%≦x≦95.8%, 4%≦y≦81.8%, 0.1%≦z≦35%, 0≦a≦40%, and 0≦b≦15%; The initial alloy melt is solidified into an initial alloy solid by a rapid solidification method, the solidification structure of the initial alloy solid includes a matrix phase and a dispersed particle phase, the matrix phase has a melting point lower than that of the dispersed particle phase, the dispersed particle phase is contained in the matrix phase, the volume percentage content of the matrix phase in the solidification structure is 40% or more, and the average composition of the matrix phase is mainly La x1 M a1 The composition of the dispersed particle phase is mainly Fe y2 T z2 M a2 D b2 La x2 Step 2, in which x1, a1, x2, y2, z2, a2, and b2 respectively represent the atomic percentage contents of the corresponding constituent elements, and 45%≦x1≦100%, 0%≦a1≦55%, 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, and 0<x2≦5%, the dispersed particle phase includes a substantial amount of spherical or nearly spherical dispersed particle phase, a portion of the spherical or nearly spherical dispersed particle phase includes specific dendritic features, and the particle size of the dispersed particle phase is 5 nm to 50 μm; Including, An alloy solid produced by the method for producing an initial alloy solid according to steps 1 and 2 of claim 1.

17. Use of the spherical iron alloy powder material according to claim 4 in the field of magnetic fluids.

18. The spherical iron alloy powder is uniformly mixed with a carrier fluid and a surfactant to obtain a magnetic fluid, Some features of the spherical iron alloy powder material include: The main component of the spherical iron alloy powder material is Fe. y2 T z2 M a2 D b2 La x2 18. The use of spherical iron alloy powder material in the field of magnetic fluids according to claim 17, characterized in that: 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, 0<x2≦5%, 1%≦z2+b2<50%, the shape of the iron alloy powder particles is mainly spherical or near-spherical, and a portion of the spherical or near-spherical iron alloy powder particles contains certain dendritic features, the particle size of the iron alloy powder particles is 5nm to 100nm, T comprises at least one of Cr and V, M comprises at least one of Al, Ni, Co, and Si, D comprises at least one of Mo, W, and Ti, and x1, a1, x2, y2, z2, a2, and b2 respectively represent the atomic content of the corresponding constituent elements.

19. A coronavirus-shaped spherical iron alloy powder particle, the main component of the coronavirus-shaped spherical iron alloy powder particle is Fe y2 T z2 M a2 D b2 La x2 and 50%≦y2≦98%, 0.2%≦z2<50%, 0%≦a2≦30%, 0%≦b2≦35%, and 0<x2≦5%; T includes at least one of Cr and V; M includes at least one of Al, Ni, Co, and Si; D includes at least one of Mo, W, and Ti; La is a rare earth element, and La is mainly Fe. y2 T z2 M a2 D b2 La x2 wherein x1, a1, x2, y2, z2, a2 ​​and b2 each represent the atomic percentage content of the corresponding constituent elements, the coronavirus-shaped spherical iron alloy powder particles include a main portion and an appendage portion, the main portion is a sphere or a sphere close to a sphere, the appendage portion is a plurality of protrusions grown in situ on the surface of the sphere of the main portion, the spherical iron alloy powder particles have a shape similar to a coronavirus, and the plurality of protrusions of the appendage portion correspond to the plurality of crown protrusions of the coronavirus shape, the diameter of the main portion of the coronavirus-shaped spherical iron alloy powder particles is 20 nm to 50 μm, and the height of the protrusions of the appendage portion is less than 0.3 times the diameter of the sphere of the main portion.